Method for producing rubber composition
Patent Information
- Application Number
- JP2024072827
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-08-31
- Filing Date
- 2024-04-26
- Publication Date
- 2025-03-14
AI Technical Summary
【0008】 本発明によれば架橋後に機械的物性および耐水性に優れた架橋ゴム組成物が得られるゴム組成物の製造方法が提供される。さらに、本発明によれば、前記ゴム組成物を用いた架橋ゴム製品の製造方法が提供される。
Smart Images

Figure 2025036065000005 
Figure 2025036065000006 
Figure 2025036065000007
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a rubber composition. [Background technology]
[0002] In recent years, materials using renewable natural fibers have been attracting attention due to the need to replace petroleum resources and growing environmental awareness. Among natural fibers, fibrous cellulose with a fiber diameter of 10 μm to 50 μm, especially fibrous cellulose (pulp) derived from wood, has been widely used mainly for paper products.
[0003] As fibrous cellulose, fine fibrous cellulose with an average fiber width of 1000 nm or less is also known. Fine fibrous cellulose has attracted attention as a new material and has a wide range of uses. For example, the development of sheets, resin composites, and thickeners containing fine fibrous cellulose is underway. In addition, composite materials in which fine fibrous cellulose is combined with resin emulsions and / or rubber latex are being considered.
[0004] Cited Document 1 discloses a composition containing a base rubber, a maleic anhydride modified polymer, and non-chemically modified and unmodified cellulose nanofibers, with the aim of providing a composition in which cellulose nanofibers are defibrated and dispersed and from which crosslinked rubber having excellent tensile properties can be produced. Patent Document 2 discloses a polymer composition comprising (I) a polymer; (II) a nanocellulose dispersion composition (NDC) comprising: (i) a carbon black filler, an elastomer latex, a wax, or any combination thereof; and (ii) nanocellulose; and (III) a carbon black additive, for the purpose of providing a method for significantly improving the dispersibility of nanocellulose in a polymer blend. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2021-123639 A [Patent Document 2] Special Publication No. 2022-508946 Summary of the Invention [Problem to be solved by the invention]
[0006] References 1 and 2 disclose compositions containing cellulose nanofibers and an elastomer, a base rubber, and the like. The present inventors have found that, in a rubber composition containing fibrous cellulose including cellulose nanofibers, although mechanical properties are improved, water resistance tends to decrease. Such a decrease in water resistance is not discussed in References 1 and 2. The present invention aims to provide a method for producing a rubber composition which can provide a crosslinked rubber composition having excellent mechanical properties and water resistance after crosslinking, and a method for producing a crosslinked rubber product using the rubber composition. [Means for solving the problem]
[0007] The inventors have discovered that the above problem can be solved by including a contacting step in a method for producing a rubber composition, in which a solid rubber composition containing a rubber component and fibrous cellulose is brought into contact with a liquid containing water. The present invention relates to the following <1> ~ <8> Regarding. <1> A method for producing a rubber composition, comprising: a step of preparing a solid rubber composition containing a rubber component and fibrous cellulose; a water contacting step of bringing the solid rubber composition into contact with a liquid containing water; and a drying step of drying the solid rubber composition that has been contacted with the liquid containing water. <2> In the water contact step, the temperature of the water-containing liquid is 60° C. or higher. <1> A method for producing the rubber composition according to claim 1. <3> The fibrous cellulose contains fine fibrous cellulose having a fiber width of 1,000 nm or less. <1> or <2> A method for producing the rubber composition according to claim 1. <4> The fibrous cellulose contains coarse cellulose fibers having a fiber width of more than 1 μm. <1> ~ <3> 13. A method for producing the rubber composition according to claim 12. <5> The step of preparing the solid rubber composition includes a step of mixing a latex containing a rubber component with an aqueous dispersion containing fibrous cellulose to obtain a mixed liquid, and a step of drying the mixed liquid. <1> ~ <4> 13. A method for producing the rubber composition according to claim 12. <6> the step of preparing the solid rubber composition includes, in this order, a step of mixing a latex containing a rubber component with an aqueous dispersion containing fibrous cellulose to obtain a mixed liquid, a step of drying the mixed liquid, and a step of masticating the obtained dried product. <1> ~ <5> 13. A method for producing the rubber composition according to claim 12. <7> the step of preparing the solid rubber composition includes, in this order, a step of mixing a latex containing a rubber component with an aqueous dispersion containing fibrous cellulose to obtain a mixed liquid, a step of drying the mixed liquid, a step of masticating the obtained dried product, and a step of adding the rubber component to the masticated dried product and kneading the mixture. <1> ~ <6> 13. A method for producing the rubber composition according to claim 12. <8> <1> ~ <7> and crosslinking and molding a molding rubber composition containing the rubber composition. Effect of the Invention
[0008] According to the present invention, there is provided a method for producing a rubber composition which can provide a crosslinked rubber composition having excellent mechanical properties and water resistance after crosslinking. Furthermore, according to the present invention, there is provided a method for producing a crosslinked rubber product using the rubber composition. [Brief description of the drawings]
[0009] [Figure 1] 1 is a graph showing the relationship between the amount of NaOH dropped onto a slurry containing fine fibrous cellulose having phosphorus oxoacid groups and pH. [Diagram 2]1 is a graph showing the relationship between the amount of NaOH dropped onto a slurry containing fibrous cellulose having a carboxy group and pH. [Diagram 3] FIG. 1 is a schematic side cross-sectional view of a double drum dryer, which is an example of a heating cylindrical dryer. [Figure 4] FIG. 1 is a schematic side view of a double drum dryer, which is an example of a heating cylindrical dryer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] [Method of manufacturing rubber composition] The method for producing a rubber composition of this embodiment includes a step of preparing a solid rubber composition containing a rubber component and fibrous cellulose, a water contacting step of bringing the solid rubber composition into contact with a liquid containing water, and a drying step of drying the solid rubber composition that has come into contact with the liquid containing water. According to the method for producing a rubber composition of the present invention, there is provided a rubber composition which can give a crosslinked rubber composition having excellent mechanical properties and water resistance after crosslinking. Although the detailed reason why the above effect is obtained is unclear, it is speculated as follows. It is believed that by contacting the solid rubber composition with a liquid containing water, at least a part of the impurities in the solid rubber composition is removed, thereby improving the water resistance. In a crosslinked rubber composition, high water resistance means that the crosslinked rubber composition has a low water absorption rate after immersion in water. Moreover, high mechanical properties means high 50% modulus, high tensile strength, and high elongation at break. The present invention will be described in detail below.
[0011] [Step of preparing a solid rubber composition containing a rubber component and fibrous cellulose] The solid rubber composition contains at least a rubber component and fibrous cellulose. The solid rubber composition is sufficient as long as it contains at least a rubber component and fibrous cellulose, and may contain other components. The solid rubber composition is a solid rubber composition that is subjected to the water contact step. As described below, the solid rubber composition may be a rubber mixture obtained by mixing a dispersion of rubber latex and fibrous cellulose and drying it, or it may be a rubber mixture obtained by masticating the rubber mixture (masticated rubber composition), or it may be a rubber mixture obtained by masticating and then kneading the rubber mixture with a rubber component (rubber kneaded product), or it may be a rubber mixture obtained by masticating and then kneading the rubber component, zinc oxide, a crosslinking accelerator, an anti-aging agent, a reinforcing material, etc. (rubber kneaded product), or it may be a crosslinked rubber composition obtained by crosslinking a rubber compound obtained by kneading a crosslinking agent into the masticated rubber composition or the rubber kneaded product, or a crosslinked rubber product obtained by crosslinking and molding the rubber compound. Among these, the solid rubber composition subjected to the water contact step is preferably a rubber mixture or a rubber mixture masticated thereto (masticated rubber composition), or a rubber mixture kneaded with, for example, a rubber component (also called a rubber kneaded product). When the solid rubber composition is a rubber mixture, a masticated rubber composition or a rubber kneaded product, the total content of the rubber component and the fibrous cellulose in the solid rubber composition is preferably 60 mass% or more, more preferably 80 mass% or more, even more preferably 90 mass% or more, still more preferably 95 mass% or more, even more preferably 99 mass% or more, and is 100 mass% or less. Each component contained in the solid rubber composition will be described in detail below.
[0012] (Rubber component) In the present embodiment, the solid rubber composition contains a rubber component. As the rubber component, for example, natural rubber (NR) or synthetic rubber can be used. Examples of synthetic rubbers include styrene-butadiene rubber (SBR), nitrile rubber, chloroprene rubber (CR), ethylene propylene rubber (EPDM), butyl rubber (IIR), chlorobutyl rubber (CIIR), acrylic rubber (ACM), silicone rubber (Q), fluororubber (FKM), butadiene rubber (BR), epoxidized butadiene rubber (EBR), epichlorohydrin rubber (CO, CEO), urethane rubber (U), and polysulfide rubber (T). Nitrile rubber includes nitrile rubber (NBR), which is a copolymer of butadiene and acrylonitrile, as well as modified products thereof, such as hydrogenated nitrile rubber, carboxyl-modified nitrile rubber, silicone-modified nitrile rubber, maleic acid-modified nitrile rubber, hydroxyl-modified nitrile rubber, and hydrogenated versions of these; and acrylonitrile-butadiene-isoprene copolymers in which part of the butadiene has been replaced with isoprene. Hydrogenated nitrile rubber (H-NBR) is sometimes called hydrogenated nitrile rubber or hydrogenated acrylonitrile-butadiene rubber. Hydrogenated nitrile rubber can be obtained by hydrogenating the double bonds contained in nitrile rubber. Natural rubber includes natural rubber (NR), as well as modified natural rubber such as epoxidized natural rubber (ENR), hydrogenated natural rubber, and deproteinized natural rubber. These rubber components may be used alone or in combination of two or more.
[0013] Among these, the rubber component is preferably at least one selected from natural rubber, nitrile rubber, butadiene rubber, and styrene-butadiene rubber, more preferably at least one selected from natural rubber, carboxylated nitrile rubber, and styrene-butadiene rubber, and even more preferably at least one selected from natural rubber, nitrile rubber (NBR), carboxy group-modified nitrile rubber, and styrene-butadiene rubber. The rubber component is preferably mixed with the fibrous cellulose as a rubber component latex. By using the rubber component latex, the dispersibility of the fibrous cellulose is improved, and it becomes easier to obtain a crosslinked rubber composition and a crosslinked rubber product having excellent mechanical properties. When using a rubber component latex, a solid rubber component may be further mixed in. The solid rubber component may be added after the rubber mixture is masticated or may be added when preparing the rubber compound, but is preferably added after the rubber mixture is masticated.
[0014] In the rubber composition of this embodiment, the content of fibrous cellulose per 100 parts by mass of the rubber component, from the viewpoint of obtaining a rubber composition having excellent properties after crosslinking, is preferably 1 part by mass or more and 200 parts by mass or less, more preferably 2 parts by mass or more, even more preferably 4 parts by mass or more, still more preferably 8 parts by mass or more, even more preferably 12 parts by mass or more, still more preferably 15 parts by mass or more, and is preferably 150 parts by mass or less, more preferably 100 parts by mass or less, even more preferably 80 parts by mass or less, still more preferably 60 parts by mass or less, even more preferably 40 parts by mass or less, and even more preferably 30 parts by mass or less.
[0015] (fibrous cellulose) In this embodiment, the solid rubber composition contains a fibrous cellulose component. The fibrous cellulose may be fine fibrous cellulose having a fiber width of 1,000 nm or less, or may be coarse cellulose fibers having a fiber width of more than 1,000 nm. Among these, it is preferable to contain fine fibrous cellulose having a fiber width of 1,000 nm, and in addition to the fine fibrous cellulose, coarse cellulose fibers may be contained.
[0016] <Fine fibrous cellulose> The fine fibrous cellulose is not particularly limited, and any known fine fibrous cellulose can be used. The upper limit of the fiber width of the fine fibrous cellulose is 1000 nm or less, preferably 100 nm or less, more preferably 50 nm or less, even more preferably 20 nm or less, and still more preferably 10 nm or less.
[0017] The average fiber width of the fine fibrous cellulose is, for example, 1000 nm or less. The average fiber width of the fine fibrous cellulose is, for example, preferably 2 nm or more and 1000 nm or less, more preferably 2 nm or more and 100 nm or less, even more preferably 2 nm or more and 50 nm or less, and even more preferably 2 nm or more and 10 nm or less. The fine fibrous cellulose is, for example, a single fiber cellulose.
[0018] The fiber width of fine fibrous cellulose is measured, for example, using an electron microscope as follows. First, an aqueous suspension of fine fibrous cellulose with a concentration of 0.05% by mass or more and 0.1% by mass or less is prepared, and this suspension is cast on a hydrophilically treated carbon film-coated grid to prepare a sample for TEM observation. When wide fibers are included, an SEM image of the surface cast on glass may be observed. Next, observation is performed using an electron microscope image at a magnification of 1000x, 5000x, 10000x, or 50000x depending on the width of the fiber to be observed. However, the sample, observation conditions, and magnification are adjusted to satisfy the following conditions. (1) A straight line X is drawn at any point within the observed image, and 20 or more fibers intersect with the straight line X. (2) Within the same image, draw a line Y that intersects the line perpendicularly, and have 20 or more fibers intersect with the line Y. For the observation images that satisfy the above conditions, the widths of the fibers that intersect with the lines X and Y are visually read. In this manner, three or more sets of observation images of at least the surface portions that do not overlap each other are obtained. Next, for each image, the widths of the fibers that intersect with the lines X and Y are read. In this manner, the widths of at least 20 fibers x 2 x 3 = 120 fibers are read. The average of the read fiber widths is then determined as the number average fiber width of the fine fibrous cellulose.
[0019] The fiber length of the fine fibrous cellulose is not particularly limited, but is preferably 0.1 μm to 1000 μm, more preferably 0.1 μm to 800 μm, and even more preferably 0.1 μm to 600 μm. By setting the fiber length within the above range, destruction of the crystalline region of the fine fibrous cellulose can be suppressed. The fiber length of the fine fibrous cellulose can be determined by image analysis using, for example, TEM, SEM, or AFM.
[0020] The fine fibrous cellulose preferably has an I-type crystal structure. The fact that the fine fibrous cellulose has an I-type crystal structure can be identified from a diffraction profile obtained from a wide-angle X-ray diffraction photograph using CuKα (λ=1.5418 Å) monochromatized with graphite. Specifically, it can be identified from the presence of typical peaks at two positions, around 2θ=14° to 17° and around 2θ=22° to 23°. The proportion of I-type crystal structure in the fine fibrous cellulose is, for example, preferably 30% or more, more preferably 40% or more, and even more preferably 50% or more. The degree of crystallinity can be determined by measuring an X-ray diffraction profile and using the pattern in a conventional manner (Seagal et al., Textile Research Journal, Vol. 29, p. 786, 1959).
[0021] The axial ratio (fiber length / fiber width) of the fine fibrous cellulose is not particularly limited, but is preferably 50 to 10,000, more preferably 100 to 1,000. By making the axial ratio equal to or greater than the lower limit, it becomes easier to form a rubber composition containing the fine fibrous cellulose. By making the axial ratio equal to or less than the upper limit, it is preferable in that, for example, when the fine fibrous cellulose is treated as a dispersion, it becomes easier to handle the fine fibrous cellulose, such as diluting the fine fibrous cellulose.
[0022] In this embodiment, the fine fibrous cellulose has, for example, both crystalline and non-crystalline regions. The fine fibrous cellulose having both crystalline and non-crystalline regions and having an axial ratio within the above range is realized by the method for producing fine fibrous cellulose described later.
[0023] In this embodiment, the fine fibrous cellulose preferably has an ionic substituent. The ionic substituent may include, for example, either one or both of an anionic group and a cationic group. In this embodiment, it is particularly preferable that the ionic substituent has an anionic group. In addition, the ionic substituent is preferably a group that is introduced into the fine fibrous cellulose via an ester bond or an ether bond, and more preferably a group that is introduced into the fine fibrous cellulose via an ester bond. In this case, the ester bond is preferably formed by dehydration condensation of the fine fibrous cellulose and a compound that becomes an ionic substituent.
[0024] Examples of anionic groups as ionic groups include phosphorus oxoacid groups or substituents derived from phosphorus oxoacid groups (sometimes simply referred to as phosphorus oxoacid groups), carboxy groups or substituents derived from carboxy groups (sometimes simply referred to as carboxy groups), sulfur oxoacid groups or substituents derived from sulfur oxoacid groups (sometimes simply referred to as sulfur oxoacid groups), xanthate groups or substituents derived from xanthate groups (sometimes simply referred to as xanthate groups), phosphonic groups or substituents derived from phosphonic groups, phosphine groups or substituents derived from phosphine groups, sulfone groups or substituents derived from sulfone groups, and carboxyalkyl groups. Among them, the anionic group is preferably at least one selected from the group consisting of phosphorus oxoacid groups, substituents derived from phosphorus oxoacid groups, carboxy groups, sulfur oxoacid groups, substituents derived from sulfur oxoacid groups, carboxymethyl groups, carboxyethyl groups, and sulfone groups, more preferably at least one selected from the group consisting of phosphorus oxoacid groups, substituents derived from phosphorus oxoacid groups, carboxy groups, sulfur oxoacid groups, and substituents derived from sulfur oxoacid groups, and even more preferably a phosphorus oxoacid group. By introducing a phosphorus oxoacid group as the anionic group, the dispersibility of the fine fibrous cellulose can be further increased even under alkaline or acidic conditions, and as a result, a sheet excellent in hardness, strength, and elongation can be easily obtained. Examples of the cationic group as the ionic group include an ammonium group, a phosphonium group, a sulfonium group, etc. Among these, the cationic group is preferably an ammonium group.
[0025] The phosphorus oxoacid group or the substituent derived from the phosphorus oxoacid group is, for example, a substituent represented by the following formula (1). A plurality of substituents represented by the following formula (1) may be introduced into each fine fibrous cellulose. In this case, the plurality of introduced substituents represented by the following formula (1) may be the same or different.
[0026] [ka] In formula (1), a, b, and n are natural numbers, and m is an arbitrary number (where a=b×m). At least one of the n α and α' is O. - and the rest are R or OR. Note that all of α and α' are O - The n α's may all be the same or may be different. b+ is a cation of one or more valences consisting of organic or inorganic substances.
[0027] Each R is a hydrogen atom, a saturated linear hydrocarbon group, a saturated branched hydrocarbon group, a saturated cyclic hydrocarbon group, an unsaturated linear hydrocarbon group, an unsaturated branched hydrocarbon group, an unsaturated cyclic hydrocarbon group, an aromatic group, or a group derived therefrom. In formula (1), n is preferably 1.
[0028] Examples of saturated linear hydrocarbon groups include, but are not limited to, methyl, ethyl, n-propyl, or n-butyl groups. Examples of saturated branched hydrocarbon groups include, but are not limited to, i-propyl or t-butyl groups. Examples of saturated cyclic hydrocarbon groups include, but are not limited to, cyclopentyl or cyclohexyl groups. Examples of unsaturated linear hydrocarbon groups include, but are not limited to, vinyl or allyl groups. Examples of unsaturated branched hydrocarbon groups include, but are not limited to, i-propenyl or 3-butenyl groups. Examples of unsaturated cyclic hydrocarbon groups include, but are not limited to, cyclopentenyl or cyclohexenyl groups. Examples of aromatic groups include, but are not limited to, phenyl or naphthyl groups.
[0029] In addition, the derivative group in R is a carboxy group, a carboxylate group (-COO - ), a functional group in which at least one selected from functional groups such as a hydroxyl group, an amino group, and an ammonium group is added or substituted, but is not particularly limited. The number of carbon atoms constituting the main chain of R is not particularly limited, but is preferably 20 or less, more preferably 10 or less. By setting the number of carbon atoms constituting the main chain of R within the above range, the molecular weight of the phosphorus oxoacid group can be set to an appropriate range, which facilitates penetration into the fiber raw material and increases the yield of fine fibrous cellulose. When multiple Rs are present in formula (1) or multiple types of substituents represented by formula (1) are introduced into the fine fibrous cellulose, the multiple Rs present may be the same or different.
[0030] β b+is a monovalent or higher cation made of an organic or inorganic substance. An example of the monovalent or higher cation made of an organic substance is an organic onium ion. An example of the organic onium ion is an organic ammonium ion or an organic onium ion. An example of the organic ammonium ion is an aliphatic ammonium ion or an aromatic ammonium ion, and an example of the organic onium ion is an aliphatic phosphonium ion or an aromatic phosphonium ion. An example of the monovalent or higher cation made of an inorganic substance is an ion of an alkali metal such as sodium, potassium, or lithium, an ion of a divalent metal such as calcium or magnesium, a hydrogen ion, an ammonium ion, or the like. In addition, in formula (1), β b+ When a plurality of β b+ may be the same or different. The organic or inorganic cations of monovalent or higher include β b+ Sodium or potassium ions are preferred because they are less likely to yellow when the fiber raw material containing the cation is heated and are easy to use industrially, but there is no particular limitation.
[0031] More specifically, the phosphorus oxo acid group or a substituent derived from the phosphorus oxo acid group is a phosphoric acid group (-PO 3 H 2 ), salts of phosphoric acid groups, phosphorous acid groups (phosphonic acid groups) (-PO 2 H 2 ), and salts of phosphorous acid group (phosphonic acid group). The phosphorus oxoacid group or the substituent derived from the phosphorus oxoacid group may be a group condensed with a phosphoric acid group (e.g., a pyrophosphate group), a group condensed with a phosphonic acid (e.g., a polyphosphonic acid group), a phosphoric ester group (e.g., a monomethyl phosphate group, a polyoxyethylene alkyl phosphate group), an alkyl phosphonic acid group (e.g., a methyl phosphonic acid group), and the like.
[0032] The sulfur oxoacid group (sulfur oxoacid group or a substituent derived from a sulfur oxoacid group) is, for example, a substituent represented by the following formula (2). A plurality of types of the substituent represented by the following formula (2) may be introduced into each fine fibrous cellulose. In this case, the plurality of introduced substituents represented by the following formula (2) may be the same or different.
[0033] [ka]
[0034] In formula (2), b and n are natural numbers, p is 0 or 1, and m is an arbitrary number (where 1=b×m). When n is 2 or more, the multiple p's may be the same or different numbers. In formula (2), β b+ is a monovalent or higher cation made of an organic or inorganic substance. An example of the monovalent or higher cation made of an organic substance is an organic onium ion. An example of the organic onium ion is an organic ammonium ion or an organic onium ion. An example of the organic ammonium ion is an aliphatic ammonium ion or an aromatic ammonium ion, and an example of the organic onium ion is an aliphatic phosphonium ion or an aromatic phosphonium ion. An example of the monovalent or higher cation made of an inorganic substance is an ion of an alkali metal such as sodium, potassium, or lithium, an ion of a divalent metal such as calcium or magnesium, a hydrogen ion, an ammonium ion, or the like. When multiple types of substituents represented by formula (2) are introduced into the fine fibrous cellulose, the multiple β b+ may be the same or different. The organic or inorganic cations of monovalent or higher include β b+ Sodium or potassium ions are preferred because they are less likely to yellow when the fiber raw material containing the cation is heated and are easy to use industrially, but there is no particular limitation.
[0035] The amount of ionic substituent introduced into the fine fibrous cellulose is, for example, preferably 0.10 mmol / g or more and 5.20 mmol / g or less, more preferably 0.20 mmol / g or more, even more preferably 0.40 mmol / g or more, still more preferably 0.60 mmol / g or more, more preferably 3.65 mmol / g or less, even more preferably 3.00 mmol / g or less, still more preferably 2.50 mmol / g or less, even more preferably 2.00 mmol / g or less, even more preferably 1.50 mmol / g or less, and even more preferably 1.00 mmol / g or less, per 1 g (mass) of fine fibrous cellulose. Here, the denominator in the unit mmol / g is the ratio of the counter ion of the ionic substituent to a hydrogen ion (H + By setting the amount of ionic substituents introduced within the above range, it is possible to easily refine the fiber raw material and to increase the stability of the fine fibrous cellulose.
[0036] The amount of ionic substituents introduced into the fine fibrous cellulose can be measured, for example, by neutralization titration after subjecting the cellulose fibers to a microfibrillation treatment. In the measurement by neutralization titration, the amount introduced is measured by determining the change in pH while adding an alkali such as an aqueous sodium hydroxide solution to a slurry containing the obtained fine fibrous cellulose.
[0037] 1 is a graph showing the relationship between the amount of NaOH dropped onto a slurry containing fine fibrous cellulose having phosphorus oxo acid groups and pH. The amount of phosphorus oxo acid groups introduced into the fine fibrous cellulose is measured, for example, as follows. First, ion-exchanged water is added to the cellulose fiber to prepare a slurry with a solid content of 0.2% by mass. This slurry is treated four times with a wet pulverizer (Starburst, manufactured by Sugino Machine Co., Ltd.) at a pressure of 200 MPa to obtain a fine fibrous cellulose dispersion (slurry) containing fine fibrous cellulose. The fine fibrous cellulose dispersion is then treated with a strong acid ion-exchange resin. Next, the change in pH is observed while adding the aqueous sodium hydroxide solution, and a titration curve such as that shown in the upper part of Figure 1 is obtained. In the titration curve shown in the upper part of Figure 1, the measured pH is plotted against the amount of alkali added, and in the titration curve shown in the lower part of Figure 1, the increment (derivative value) of pH (1 / mmol) against the amount of alkali added is plotted. In this neutralization titration, two points are confirmed in the curve plotting the measured pH against the amount of alkali added, where the increment (derivative value of pH against the amount of alkali added) is maximum. Of these, the first maximum point of the increment obtained after starting to add the alkali is called the first endpoint, and the next maximum point of the increment is called the second endpoint. The amount of alkali required from the start of titration to the first end point is equal to the amount of the first dissociated acid of the fine fibrous cellulose contained in the slurry used for titration, the amount of alkali required from the first end point to the second end point is equal to the amount of the second dissociated acid of the fine fibrous cellulose contained in the slurry used for titration, and the amount of alkali required from the start of titration to the second end point is equal to the total amount of dissociated acid of the fine fibrous cellulose contained in the slurry used for titration. The value obtained by dividing the amount of alkali required from the start of titration to the first end point by the solid content (g) in the slurry to be titrated is the amount of phosphorus oxoacid group introduced (mmol / g). Note that when simply referring to the amount of phosphorus oxoacid group introduced (or the amount of phosphorus oxoacid group), it refers to the amount of the first dissociated acid. In FIG. 1, the region from the start of titration to the first end point is called the first region, and the region from the first end point to the second end point is called the second region. For example, when the phosphorus oxoacid group is a phosphate group and this phosphate group undergoes condensation, the amount of weak acid groups in the phosphorus oxoacid group (also referred to as the second dissociated acid amount in this specification) appears to decrease, and the amount of alkali required in the second region becomes smaller than the amount of alkali required in the first region. On the other hand, the amount of strong acid groups in the phosphorus oxoacid group (also referred to as the first dissociated acid amount in this specification) is equal to the amount of phosphorus atoms regardless of the presence or absence of condensation. In addition, when the phosphorus oxoacid group is a phosphorous acid group, the phosphorus oxoacid group no longer has weak acid groups, so the amount of alkali required in the second region becomes smaller or may become zero. In this case, there is only one point on the titration curve where the pH increment is maximum.
[0038] The above-mentioned amount of phosphorus oxoacid groups introduced (mmol / g) indicates the amount of phosphorus oxoacid groups in the acid-type fine fibrous cellulose (hereinafter referred to as the amount of phosphorus oxoacid groups (acid type)), since the denominator indicates the mass of the acid-type fine fibrous cellulose. On the other hand, when the counter ion of the phosphorus oxoacid group is replaced with any cation C so as to be the charge equivalent, the amount of phosphorus oxoacid groups in the fine fibrous cellulose in which the cation C is the counter ion (hereinafter referred to as the amount of phosphorus oxoacid groups (C type)) can be obtained by converting the denominator to the mass of the fine fibrous cellulose when the cation C is the counter ion. That is, it is calculated by the following formula. Phosphorus oxoacid group content (C type) = amount of phosphorus oxoacid groups (acid type) / {1+(W-1)×P / 1000} P [mmol / g]: total amount of anions derived from phosphorus oxoacid groups in fibrous cellulose (total amount of dissociated acid from phosphorus oxoacid groups) W: Formula weight per valence of cation C (e.g., Na is 23, Al is 9)
[0039] 2 is a graph showing the relationship between the amount of NaOH dropped onto a dispersion of fine fibrous cellulose having a carboxy group as an ionic substituent and pH. The amount of carboxy group introduced into the fine fibrous cellulose is measured, for example, as follows. First, ion-exchanged water is added to the cellulose fiber to prepare a slurry with a solid content of 0.2% by mass. This slurry is treated four times with a wet pulverizer (Starburst, manufactured by Sugino Machine Co., Ltd.) at a pressure of 200 MPa to obtain a fine fibrous cellulose dispersion (slurry) containing fine fibrous cellulose. The fine fibrous cellulose dispersion is then treated with a strong acid ion-exchange resin. Next, the change in pH is observed while adding the aqueous sodium hydroxide solution, and a titration curve as shown in the upper part of FIG. 2 is obtained. In the titration curve shown in the upper part of FIG. 2, the measured pH is plotted against the amount of added alkali, and in the titration curve shown in the lower part of FIG. 2, the increment (differential value) (1 / mmol) of pH against the amount of added alkali is plotted. In this neutralization titration, one point where the increment (differential value of pH against the amount of added alkali) is maximum is confirmed in the curve plotting the measured pH against the amount of added alkali, and this maximum point is called the first end point. Here, the region from the start of titration to the first end point in FIG. 2 is called the first region. The amount of alkali required in the first region is equal to the amount of carboxyl groups in the dispersion used for titration. The amount of alkali required in the first region of the titration curve (mmol) is divided by the solid content (g) in the dispersion containing the fine fibrous cellulose to be titrated to calculate the amount of carboxyl groups introduced (mmol / g).
[0040] The above-mentioned amount of carboxyl groups introduced (mmol / g) indicates the amount of carboxyl groups in the acid-type fine fibrous cellulose (hereinafter referred to as the amount of carboxyl groups (acid type)) since the denominator is the mass of the acid-type fine fibrous cellulose. On the other hand, when the counter ion of the carboxyl group is replaced with any cation C so as to be the charge equivalent, the amount of carboxyl groups in the fine fibrous cellulose in which the cation C is the counter ion (hereinafter referred to as the amount of carboxyl groups (C type)) can be obtained by converting the denominator to the mass of the fine fibrous cellulose when the cation C is the counter ion. That is, it is calculated by the following formula. Carboxylic acid content (C type) = amount of carboxyl group (acid type) / {1+(W-1)×(amount of carboxyl group (acid type)) / 1000} W: Formula weight per valence of cation C (e.g., Na is 23, Al is 9)
[0041] In measuring the amount of ionic substituents by titration, if the amount of sodium hydroxide solution dropped is too large or the titration interval is too short, the amount of ionic substituents may be lower than the actual amount, and an accurate value may not be obtained. For example, a suitable amount of drop and titration interval is preferably 10 to 50 μL of 0.1N sodium hydroxide solution titrated every 5 to 30 seconds. In addition, in order to eliminate the influence of carbon dioxide dissolved in the fine fibrous cellulose dispersion, it is preferable to measure while blowing an inert gas such as nitrogen gas into the slurry from 15 minutes before the start of titration until the end of titration.
[0042] The amount of sulfate ester groups and sulfone groups introduced into the fine fibrous cellulose was determined by wet ashing the obtained fine fibrous cellulose using perchloric acid and concentrated nitric acid, diluting it at an appropriate ratio, and measuring the amount of sulfur by ICP atomic emission spectrometry. The amount of sulfur thus determined was divided by the bone dry mass of the fine fibrous cellulose tested, and this value was taken as the amount of sulfur oxoacid groups and sulfonic groups (unit: mmol / g).
[0043] In order to obtain the fine fibrous cellulose having the ionic substituent introduced therein, it is preferable to have an ionic substituent introduction step for introducing an ionic substituent into a fiber raw material containing cellulose, a washing step, an alkali treatment step (neutralization step), and a defibration treatment step in this order, and an acid treatment step may be included instead of or in addition to the washing step. Examples of the ionic substituent introduction step include a phosphorus oxo acid group introduction step, a carboxy group introduction step, a sulfur oxo acid group introduction step, a xanthate group introduction step, a phosphonic or phosphine group introduction step, a sulfonic group introduction step, and a cationic group introduction step. Each of these steps will be described below.
[0044] <Textile raw materials> The fiber raw material is a fiber raw material containing cellulose, and examples of the fiber raw material include, but are not limited to, wood pulp, non-wood pulp, and deinked pulp. Examples of wood pulp include, but are not limited to, chemical pulp such as hardwood kraft pulp (LBKP), softwood kraft pulp (NBKP), sulfite pulp (SP), dissolving pulp (DP), soda pulp (AP), unbleached kraft pulp (UKP), and oxygen bleached kraft pulp (OKP), semi-chemical pulp such as semi-chemical pulp (SCP) and chemi-ground wood pulp (CGP), and mechanical pulp such as groundwood pulp (GP) and thermomechanical pulp (TMP, BCTMP). Examples of non-wood pulp include, but are not limited to, cotton-based pulp such as cotton linters and cotton lint, and non-wood-based pulp such as hemp, straw, bamboo, and bagasse. Examples of deinked pulp include, but are not limited to, deinked pulp made from waste paper. The pulp raw material of this embodiment may be one of the above-mentioned materials, or a mixture of two or more of them. Among the above pulps, for example, wood pulp and deinked pulp are preferred from the viewpoint of availability. Furthermore, among wood pulps, for example, chemical pulp is more preferred, and kraft pulp and sulfite pulp are even more preferred, from the viewpoint of high cellulose ratio and high yield of fine fibrous cellulose during defibration treatment, and small decomposition of cellulose in the pulp to obtain long-fiber fine fibrous cellulose with a large axial ratio. Note that the viscosity tends to increase when long-fiber fine fibrous cellulose with a large axial ratio is used.
[0045] <Phosphorus Oxo Acid Group Introduction Step> When obtaining cellulose fibers having an ionic substituent, it is preferable to provide an ionic substituent introduction step before the microfine treatment step. An example of the ionic substituent introduction step is a phosphorus oxo acid group introduction step. The phosphorus oxo acid group introduction step is a step of allowing at least one compound (hereinafter also referred to as "compound A") selected from compounds capable of introducing a phosphorus oxo acid group by reacting with a hydroxyl group possessed by a fiber raw material containing cellulose to act on the fiber raw material containing cellulose. This step results in the production of cellulose fibers having a phosphorus oxo acid group.
[0046] In the phosphorus oxoacid group introduction step according to this embodiment, the reaction of the cellulose-containing fiber raw material with compound A may be carried out in the presence of at least one selected from urea and its derivatives (hereinafter also referred to as "compound B"). Alternatively, the reaction of the cellulose-containing fiber raw material with compound A may be carried out in the absence of compound B.
[0047] An example of a method for acting compound A on a fiber raw material in the presence of compound B includes a method of mixing compound A and compound B with a fiber raw material in a dry state, a wet state, or a slurry state. Of these, it is preferable to use a fiber raw material in a dry state or a wet state, and it is particularly preferable to use a fiber raw material in a dry state, because the reaction is highly uniform. The form of the fiber raw material is not particularly limited, but it is preferable to use, for example, a cotton-like or thin sheet-like form. Compound A and compound B can be added to the fiber raw material in a powder form, a solution form dissolved in a solvent, or a melted state by heating to a melting point or higher. Of these, it is preferable to add them in a solution form dissolved in a solvent, especially in an aqueous solution form, because the reaction is highly uniform. In addition, compound A and compound B may be added to the fiber raw material simultaneously, separately, or as a mixture. The method of adding compound A and compound B is not particularly limited, but when compound A and compound B are in a solution state, the fiber raw material may be immersed in the solution to absorb the liquid and then removed, or the solution may be dropped onto the fiber raw material. In addition, the required amounts of compound A and compound B may be added to the fiber raw material, or excess amounts of compound A and compound B may be added to the fiber raw material, respectively, and then the excess compound A and compound B may be removed by squeezing or filtration.
[0048] Compound A used in this embodiment may be any compound having a phosphorus atom and capable of forming an ester bond with cellulose, and may include, but is not limited to, phosphoric acid or a salt thereof, phosphorous acid or a salt thereof, dehydrated condensed phosphoric acid or a salt thereof, and anhydrous phosphoric acid (diphosphorus pentoxide). Phosphoric acid may be used with various purities, for example, 100% phosphoric acid (orthophosphoric acid) or 85% phosphoric acid. Phosphorous acid may be 99% phosphorous acid (phosphonic acid). Dehydrated condensed phosphoric acid is a phosphoric acid in which two or more molecules are condensed by a dehydration reaction, and examples of such include pyrophosphoric acid and polyphosphoric acid. Phosphates, phosphites, and dehydrated condensed phosphates include lithium salts, sodium salts, potassium salts, and ammonium salts of phosphoric acid, phosphorous acid, or dehydrated condensed phosphoric acid, and these may be neutralized to various degrees. Among these, from the viewpoints of high efficiency of introduction of phosphate groups, easier improvement of defibration efficiency in the defibration step described below, low cost, and ease of industrial application, phosphoric acid, sodium salt of phosphoric acid, potassium salt of phosphoric acid, ammonium salt of phosphoric acid, or phosphorous acid, sodium salt of phosphorous acid, potassium salt of phosphorous acid, or ammonium salt of phosphorous acid are preferred, and phosphoric acid, sodium dihydrogen phosphate, disodium hydrogen phosphate, ammonium dihydrogen phosphate, or phosphorous acid and sodium phosphite are more preferred.
[0049] The amount of compound A added to the fiber raw material is not particularly limited, but for example, when the amount of compound A added is converted into the amount of phosphorus atoms, the amount of phosphorus atoms added to the fiber raw material (bone dry mass) is preferably 0.5% by mass or more and 100% by mass or less, more preferably 1% by mass or more and 50% by mass or less, and even more preferably 2% by mass or more and 30% by mass or less. By setting the amount of phosphorus atoms added to the fiber raw material within the above range, the yield of fine fibrous cellulose can be further improved. On the other hand, by setting the amount of phosphorus atoms added to the fiber raw material to the above upper limit or less, a balance can be achieved between the effect of improving the yield and the cost.
[0050] The compound B used in this embodiment is at least one selected from urea and its derivatives as described above. Examples of compound B include urea, biuret, 1-phenylurea, 1-benzylurea, 1-methylurea, and 1-ethylurea. From the viewpoint of improving the uniformity of the reaction, it is preferable to use compound B as an aqueous solution. In addition, from the viewpoint of further improving the uniformity of the reaction, it is preferable to use an aqueous solution in which both compound A and compound B are dissolved.
[0051] The amount of compound B added relative to the fiber raw material (bone dry mass) is not particularly limited, but is, for example, preferably 1 mass% or more and 500 mass% or less, more preferably 10 mass% or more and 400 mass% or less, and even more preferably 100 mass% or more and 350 mass% or less.
[0052] In the reaction of a fiber raw material containing cellulose with compound A, in addition to compound B, for example, amides or amines may be included in the reaction system. Examples of amides include formamide, dimethylformamide, acetamide, and dimethylacetamide. Examples of amines include methylamine, ethylamine, trimethylamine, triethylamine, monoethanolamine, diethanolamine, triethanolamine, pyridine, ethylenediamine, and hexamethylenediamine. Among these, triethylamine in particular is known to act as a good reaction catalyst.
[0053] In the phosphorus oxo acid group introduction step, it is preferable to add or mix the compound A or the like to the fiber raw material, and then heat-treat the fiber raw material. It is preferable to select a temperature for the heat treatment that can efficiently introduce the phosphorus oxo acid group while suppressing thermal decomposition and hydrolysis of the fiber. The heat treatment temperature is, for example, preferably 50°C or higher and 300°C or lower, more preferably 100°C or higher and 250°C or lower, and even more preferably 130°C or higher and 200°C or lower. In addition, for the heat treatment, equipment having various heat media can be used, such as a stirring dryer, a rotary dryer, a disk dryer, a roll-type heater, a plate-type heater, a fluidized bed dryer, a band-type dryer, a filtration dryer, a vibration fluidized dryer, an airflow dryer, a reduced pressure dryer, an infrared heater, a far-infrared heater, a microwave heater, or a high-frequency dryer.
[0054] In this embodiment, the heat treatment may be performed by, for example, adding compound A to a thin sheet-like fiber raw material by a method such as impregnation, and then heating the material, or by heating the material while kneading or stirring the material and compound A in a kneader or the like. This makes it possible to suppress unevenness in the concentration of compound A in the fiber raw material and to more uniformly introduce phosphorus oxoacid groups onto the surface of the cellulose fibers contained in the fiber raw material. This is believed to be due to the fact that when water molecules move to the surface of the fiber raw material as it dries, the dissolved compound A is attracted to the water molecules by surface tension and is prevented from moving to the surface of the fiber raw material in the same manner (i.e., causing unevenness in the concentration of compound A).
[0055] In addition, the heating device used in the heat treatment is preferably a device that can constantly discharge, for example, the moisture held by the slurry and the moisture generated by the dehydration condensation (phosphorylation) reaction between compound A and hydroxyl groups contained in cellulose or the like in the fiber raw material, outside the device system. Examples of such heating devices include ovens that use a blowing system. By constantly discharging the moisture within the device system, it is possible to suppress the hydrolysis reaction of phosphate ester bonds, which is the reverse reaction of phosphate esterification, and also to suppress acid hydrolysis of the sugar chains in the fibers. This makes it possible to obtain fine fibrous cellulose with a high axial ratio.
[0056] The time for the heat treatment is, for example, from when moisture is substantially removed from the fiber raw material, preferably from 1 second to 300 minutes, more preferably from 1 second to 1000 seconds, and even more preferably from 10 seconds to 800 seconds. In this embodiment, the introduction amount of phosphorus oxo acid groups can be kept within a preferred range by setting the heating temperature and heating time within appropriate ranges.
[0057] The phosphorus oxo acid group introduction step may be carried out at least once, but may also be carried out twice or more. By carrying out the phosphorus oxo acid group introduction step twice or more, a large number of phosphorus oxo acid groups can be introduced into the fiber raw material.
[0058] The amount of phosphorus oxoacid groups introduced into the fiber raw material is, for example, preferably 0.10 mmol / g or more and 5.20 mmol / g or less, more preferably 0.20 mmol / g or more, even more preferably 0.50 mmol / g or more, still more preferably 1.00 mmol / g or more, and more preferably 3.65 mmol / g or less, and even more preferably 3.00 mmol / g or less, per gram (mass) of cellulose fiber. By keeping the amount of phosphorus oxoacid groups introduced within the above ranges, it is possible to facilitate the finening of cellulose fibers in the fineness treatment step and to increase the stability of fine fibrous cellulose.
[0059] Carboxy Group Introduction Step The ionic substituent introduction step may include a carboxyl group introduction step, which is carried out by subjecting a fiber raw material containing cellulose to an oxidation treatment such as ozone oxidation, oxidation by the Fenton method, or TEMPO oxidation treatment, or by treating the raw material with a compound having a carboxylic acid-derived group or a derivative thereof, or an acid anhydride of a compound having a carboxylic acid-derived group or a derivative thereof.
[0060] Examples of compounds having a group derived from a carboxylic acid include, but are not limited to, dicarboxylic acid compounds such as maleic acid, succinic acid, phthalic acid, fumaric acid, glutaric acid, adipic acid, and itaconic acid, and tricarboxylic acid compounds such as citric acid and aconitic acid. Examples of derivatives of compounds having a group derived from a carboxylic acid include, but are not limited to, imidized products of acid anhydrides of compounds having a carboxy group, and derivatives of acid anhydrides of compounds having a carboxy group. Examples of imidized products of acid anhydrides of compounds having a carboxy group include, but are not limited to, imidized products of dicarboxylic acid compounds such as maleimide, succinimide, and phthalimide.
[0061] The acid anhydride of a compound having a group derived from a carboxylic acid is not particularly limited, but examples thereof include acid anhydrides of dicarboxylic acid compounds such as maleic anhydride, succinic anhydride, phthalic anhydride, glutaric anhydride, adipic anhydride, itaconic anhydride, etc. Furthermore, the derivative of an acid anhydride of a compound having a group derived from a carboxylic acid is not particularly limited, but examples thereof include acid anhydrides of compounds having a carboxy group such as dimethylmaleic anhydride, diethylmaleic anhydride, diphenylmaleic anhydride, etc., in which at least a part of the hydrogen atoms is substituted with a substituent such as an alkyl group or a phenyl group.
[0062] When a TEMPO oxidation treatment is performed in the carboxyl group introduction step, it is preferable to perform the treatment under conditions of a pH of 6 or more and 8 or less. Such a treatment is also called a neutral TEMPO oxidation treatment. The neutral TEMPO oxidation treatment can be performed, for example, by adding pulp as a fiber raw material, a nitroxy radical such as TEMPO (2,2,6,6-tetramethylpiperidine-1-oxyl) as a catalyst, and sodium hypochlorite as a sacrificial reagent to a sodium phosphate buffer solution (pH = 6.8). Furthermore, by allowing sodium chlorite to coexist, aldehydes generated during the oxidation process can be efficiently oxidized to carboxyl groups. The TEMPO oxidation treatment may be carried out under conditions of a pH of 10 to 11. This type of treatment is also called alkaline TEMPO oxidation treatment. The alkaline TEMPO oxidation treatment can be carried out, for example, by adding a nitroxy radical such as TEMPO as a catalyst, sodium bromide as a co-catalyst, and sodium hypochlorite as an oxidizing agent to pulp as a fiber raw material.
[0063] The amount of carboxyl groups introduced into cellulose fibers varies depending on the type of the substituent, but for example, when carboxyl groups are introduced by TEMPO oxidation, the amount is preferably 0.10 mmol / g or more and 3.65 mmol / g or less per 1 g (mass) of cellulose fibers, more preferably 0.20 mmol / g or more, even more preferably 0.40 mmol / g or more, even more preferably 0.60 mmol / g or more, and more preferably 3.00 mmol / g or less, even more preferably 2.50 mmol / g or less, even more preferably 2.00 mmol / g or less, even more preferably 1.50 mmol / g or less, and even more preferably 1.00 mmol / g or less. In addition, when the substituent is a carboxymethyl group, the amount of carboxyl groups introduced may be 5.8 mmol / g or less per 1 g (mass) of cellulose fibers. By setting the amount of carboxyl groups introduced within the above range, it is possible to facilitate the fine pulverization of cellulose fibers in the fine pulverization treatment step and to increase the stability of fine fibrous cellulose.
[0064] Sulfonic group introduction step The ionic substituent introduction step may include a sulfonic group introduction step, in which a hydroxyl group in a fiber raw material containing cellulose reacts with a sulfur oxoacid to obtain a cellulose fiber having a sulfonic group (sulfonic group-introduced fiber).
[0065] In the sulfonic group introduction step, instead of the compound A in the above-mentioned <phosphorus oxo acid group introduction step>, at least one compound (hereinafter also referred to as "compound C") selected from compounds capable of introducing a sulfonic group by reacting with a hydroxyl group possessed by a fiber raw material containing cellulose is used. Compound C may be any compound having a sulfur atom and capable of forming an ester bond with cellulose, and may include, but is not limited to, sulfuric acid or a salt thereof, sulfurous acid or a salt thereof, and sulfuric acid amide. As the sulfuric acid, those of various purities may be used, for example, 96% sulfuric acid (concentrated sulfuric acid). As the sulfurous acid, 5% sulfurous acid water may be used. As the sulfate or sulfite, lithium salt, sodium salt, potassium salt, ammonium salt, and the like of sulfate or sulfite may be used, and these may be neutralized to various degrees. As the sulfuric acid amide, sulfamic acid or the like may be used. In the sulfonic group introduction step, it is preferable to use compound B in the above-mentioned <phosphorus oxo acid group introduction step> in the same manner.
[0066] In the sulfonic acid introduction step, it is preferable to mix the cellulose raw material with an aqueous solution containing sulfur oxoacid and urea and / or a urea derivative, and then heat-treat the cellulose raw material. It is preferable to select a temperature for the heat treatment that can efficiently introduce sulfonic acid groups while suppressing thermal decomposition and hydrolysis of the fibers. The heat treatment temperature is preferably 100°C or higher and 300°C or lower, more preferably 120°C or higher, even more preferably 150°C or higher, and more preferably 250°C or lower, even more preferably 200°C or lower.
[0067] In the heat treatment step, it is preferable to heat until substantially no moisture is present. For this reason, the heat treatment time varies depending on the amount of moisture contained in the cellulose raw material and the amount of the aqueous solution containing sulfur oxoacid and urea and / or urea derivative added, but is preferably 10 seconds or more and 10,000 seconds or less. For the heat treatment, various devices having heat media can be used, such as a hot air dryer, a stirring dryer, a rotary dryer, a disk dryer, a roll type heater, a plate type heater, a fluidized bed dryer, a band type dryer, a filtration dryer, a vibration fluidized dryer, an airflow dryer, a reduced pressure dryer, an infrared heater, a far infrared heater, a microwave heater, and a high frequency dryer.
[0068] The amount of sulfonic groups introduced into the cellulose raw material is preferably 0.05 mmol / g or more and 5.00 mmol / g or less, more preferably 0.10 mmol / g or more, even more preferably 0.20 mmol / g or more, still more preferably 0.40 mmol / g or more, even more preferably 0.50 mmol / g or more, and more preferably 3.00 mmol / g or less. By making the amount of sulfonic groups introduced within the above range, it is possible to facilitate the fine cellulose fibers in the fine cellulose fiber fine treatment step and to increase the stability of the fine fibrous cellulose.
[0069] <Oxidation step using a chlorine-based oxidizing agent (second carboxyl group introduction step)> The ionic substituent introduction step may include an oxidation step using a chlorine-based oxidizing agent, in which the chlorine-based oxidizing agent is added to a wet or dry fiber raw material having a hydroxyl group to cause a reaction, thereby introducing a carboxyl group into the fiber raw material.
[0070] Examples of chlorine-based oxidizing agents include hypochlorous acid, hypochlorites, chlorous acid, chlorites, chloric acid, chlorates, perchloric acid, perchlorates, and chlorine dioxide. In terms of the efficiency of introducing a substituent, and therefore the efficiency of defibration, cost, and ease of handling, the chlorine-based oxidizing agent is preferably sodium hypochlorite, sodium chlorite, or chlorine dioxide. When adding a chlorine-based oxidizing agent, it may be added to the fiber raw material as it is as a reagent (solid or liquid), or it may be added after dissolving in an appropriate solvent.
[0071] The concentration of the chlorine-based oxidizing agent in the solution in the oxidation step using the chlorine-based oxidizing agent is, for example, converted into an effective chlorine concentration, preferably 1% by mass to 1,000% by mass, more preferably 5% by mass to 500% by mass, and even more preferably 10% by mass to 100% by mass. The amount of the chlorine-based oxidizing agent added per 100 parts by mass of the fiber raw material is preferably 1 part by mass to 100,000 parts by mass, more preferably 10 parts by mass to 10,000 parts by mass, and even more preferably 100 parts by mass to 5,000 parts by mass.
[0072] The reaction time with the chlorine-based oxidizing agent in the oxidation step using the chlorine-based oxidizing agent may vary depending on the reaction temperature, but is, for example, preferably 1 minute to 1,000 minutes, more preferably 10 minutes to 500 minutes, and even more preferably 20 minutes to 400 minutes. The pH during the reaction is preferably 5 to 15, more preferably 7 to 14, and even more preferably 9 to 13. At the start of the reaction, the pH during the reaction is preferably kept constant (for example, pH 11) by appropriately adding hydrochloric acid or sodium hydroxide. After the reaction, excess reaction reagents, by-products, etc. may be washed with water and removed by filtration or the like.
[0073] <Xanthate group introduction process> The manufacturing process of the fine fibrous cellulose may include a xanthate group introduction step as an ionic substituent introduction step. In the xanthate group introduction step, a hydroxyl group of a fiber raw material containing cellulose is replaced with a xanthate group represented by the following formula (3), thereby obtaining a cellulose fiber having a xanthate group (xanthate group-introduced fiber). -OCSS - M + ……(3) Here, M + is at least one selected from a hydrogen ion, a monovalent metal ion, an ammonium ion, and an aliphatic or aromatic ammonium ion.
[0074] In the xanthate group introduction step, first, the fiber raw material containing the cellulose is treated with an alkali solution to obtain alkali cellulose. Examples of the alkali solution include an alkali metal hydroxide aqueous solution and an alkaline earth metal hydroxide aqueous solution. Among them, the alkali solution is preferably an alkali metal hydroxide aqueous solution such as sodium hydroxide or potassium hydroxide, and more preferably an aqueous sodium hydroxide solution. When the alkali solution is an alkali metal hydroxide aqueous solution, the alkali metal hydroxide concentration in the alkali metal hydroxide aqueous solution is preferably 4% by mass or more and 9% by mass or less, more preferably 5% by mass or more. By setting the alkali metal hydroxide concentration to the above lower limit value or more, the mercerization of cellulose can be sufficiently promoted, the amount of by-products generated during the subsequent xanthation can be reduced, and as a result, the yield of xanthate group-introduced fiber can be increased. This makes it possible to more effectively perform the defibration treatment described later. Furthermore, by setting the alkali metal hydroxide concentration to the above upper limit or less, it is possible to prevent the aqueous alkali metal hydroxide solution from penetrating into the crystalline regions of cellulose while allowing mercerization to proceed, which makes it easier to maintain the cellulose type I crystal structure and further increases the yield of fine fibrous cellulose.
[0075] The time of the alkali treatment is preferably 30 minutes or more and 6 hours or less, more preferably 1 hour or more and 5 hours or less. By setting the time of the alkali treatment within the above range, the final yield can be increased, and the productivity can be increased.
[0076] The alkali cellulose obtained by the above-mentioned alkali treatment is preferably subjected to solid-liquid separation to remove as much aqueous solution as possible. This can reduce the water content during the subsequent xanthate treatment, and can promote the reaction. As a method for solid-liquid separation, for example, a general dehydration method such as centrifugation or filtration can be used. In addition, the concentration of alkali metal hydroxide contained in the alkali cellulose after solid-liquid separation is preferably 3% by mass or more and 8% by mass or less with respect to the total mass of the alkali cellulose after solid-liquid separation.
[0077] In the xanthate group introduction process, the xanthate formation process is carried out after the alkali treatment. In the xanthate formation process, carbon disulfide (CS 2 ) to react with (-O - Na + ) group to (-OCSS - Na + In the above, the metal ions introduced into the alkali cellulose are typically Na + However, similar reactions occur with other alkali metal ions.
[0078] In the xanthate treatment, it is preferable to supply 10% by mass or more of carbon disulfide based on the absolute dry mass of cellulose in the alkali cellulose. In addition, in the xanthate treatment, the time for which carbon disulfide and alkali cellulose are in contact is preferably 30 minutes or more, more preferably 1 hour or more. Although the xanthate formation proceeds quickly when carbon disulfide contacts alkali cellulose, it takes time for carbon disulfide to penetrate into the inside of alkali cellulose, so it is preferable to set the reaction time to the above range. On the other hand, the time for which carbon disulfide contacts alkali cellulose may be 6 hours or less, which allows sufficient penetration into the mass of alkali cellulose after dehydration, and allows the reaction-ready xanthate formation to be almost completed.
[0079] The reaction temperature in the xanthate treatment is preferably 46° C. or less. By setting the reaction temperature within the above range, it is easy to suppress the decomposition of the alkali cellulose. In addition, by setting the reaction temperature within the above range, it is easy to react uniformly, so that the generation of by-products can be suppressed, and further, the removal of the generated xanthate group can be suppressed.
[0080] The amount of xanthate group introduced in the xanthate group introduction step is preferably 0.60 mmol / g or more and 5.00 mmol / g or less per 1 g (mass) of fiber raw material, more preferably 0.70 mmol / g or more, even more preferably 0.80 mmol / g or more, even more preferably 1.00 mmol / g or more, even more preferably 1.20 mmol / g or more, and more preferably 3.00 mmol / g or less. By making the amount of xanthate group introduced within the above range, it is possible to easily refine the fiber raw material and to increase the stability of the fine fibrous cellulose.
[0081] <Phosphonic or Phosphine Group Introduction Step (Phosphoalkylation Step)> The ionic substituent introduction step may include a phosphonic or phosphine group introduction step (phosphoalkylation step). In the phosphoalkylation step, a compound having a reactive group and a phosphonic or phosphine group (compound E A ), an optional alkaline compound, and compound B selected from the above-mentioned urea and its derivatives are added to a wet or dry fiber raw material having a hydroxyl group and reacted to introduce a phosphonic or phosphine group into the fiber raw material.
[0082] Examples of the reactive group include a halogenated alkyl group, a vinyl group, and an epoxy group (glycidyl group). Compound E A Examples of the compound E include vinyl phosphonic acid, phenyl vinyl phosphonic acid, and phenyl vinyl phosphinic acid. From the viewpoints of the efficiency of introducing the substituent, the defibration efficiency, the cost, and the ease of handling, the compound E A is preferably vinylphosphonic acid. Furthermore, as an optional component, it is also preferable to use compound B in the above-mentioned <Phosphorus oxo acid group introduction step> in the same manner, and the amount added is also preferably as described above.
[0083] Compound E A When adding, it may be added to the fiber raw material as a reagent (solid or liquid) as it is, or may be dissolved in a suitable solvent and added. It is preferable that the fiber raw material is converted into alkali cellulose in advance or simultaneously with the reaction. The method of conversion into alkali cellulose is as described above.
[0084] The reaction temperature is, for example, preferably 50°C or more and 300°C or less, more preferably 100°C or more and 250°C or less, and further preferably 130°C or more and 200°C or less.
[0085] Compound E A The amount of addition per 100 parts by mass of the fiber raw material is preferably 1 part by mass to 100,000 parts by mass, more preferably 2 parts by mass to 10,000 parts by mass, and even more preferably 5 parts by mass to 1,000 parts by mass.
[0086] The reaction time may vary depending on the reaction temperature, but is, for example, preferably from 1 minute to 1,000 minutes, more preferably from 10 minutes to 500 minutes, and further preferably from 20 minutes to 400 minutes. After the reaction, excess reaction reagents, by-products, etc. may be washed and removed with water by filtration or the like.
[0087] Sulfone Group Introduction Step (Sulfoalkylation Step) (Second Sulfone Group Introduction Step) The ionic substituent introduction step may include a sulfone group introduction step (sulfoalkylation step). In the sulfoalkylation, a compound having a reactive group and a sulfone group (compound E) is used as an essential component. B ) and, as an optional component, an alkaline compound, and compound B selected from the above-mentioned urea and its derivatives are added to a wet or dry fiber raw material having a hydroxyl group and reacted to introduce a sulfone group into the fiber raw material.
[0088] Examples of the reactive group include a halogenated alkyl group, a vinyl group, and an epoxy group (glycidyl group). Compound E B Examples of suitable sulfonates include sodium 2-chloroethanesulfonate, sodium vinylsulfonate, sodium p-styrenesulfonate, and 2-acrylamido-2-methylpropanesulfonic acid. Among these, compound E is particularly preferred in terms of the efficiency of introducing substituents, and therefore the defibration efficiency, cost, and ease of handling. B is preferably sodium vinyl sulfonate. Furthermore, as an optional component, it is also preferable to use compound B in the above-mentioned <Phosphorus oxo acid group introduction step> in the same manner, and the amount added is also preferably as described above.
[0089] Compound E B When adding, it may be added to the fiber raw material as a reagent (solid or liquid) as it is, or may be dissolved in a suitable solvent and added. It is preferable that the fiber raw material is converted into alkali cellulose in advance or simultaneously with the reaction. The method of conversion into alkali cellulose is as described above.
[0090] The reaction temperature is, for example, preferably 50°C or more and 300°C or less, more preferably 100°C or more and 250°C or less, and further preferably 130°C or more and 200°C or less.
[0091] Compound E B The amount of addition per 100 parts by mass of the fiber raw material is preferably 1 part by mass to 100,000 parts by mass, more preferably 2 parts by mass to 10,000 parts by mass, and even more preferably 5 parts by mass to 1,000 parts by mass.
[0092] The reaction time may vary depending on the reaction temperature, but is, for example, preferably from 1 minute to 1,000 minutes, more preferably from 10 minutes to 500 minutes, and further preferably from 15 minutes to 400 minutes. After the reaction, excess reaction reagents, by-products, etc. may be washed and removed with water by filtration or the like.
[0093] Carboxyalkylation step (third carboxy group introduction step) The ionic substituent introduction step may include a carboxyalkylation step. As an essential component, a compound having a reactive group and a carboxy group (compound E C ), an optional alkaline compound, and compound B selected from the above-mentioned urea and its derivatives are added to a wet or dry fiber raw material having a hydroxyl group and reacted to introduce a carboxyl group into the fiber raw material.
[0094] Examples of the reactive group include a halogenated alkyl group, a vinyl group, and an epoxy group (glycidyl group). Compound E C As the chloropropionic acid, monochloroacetic acid, sodium monochloroacetate, 2-chloropropionic acid, 3-chloropropionic acid, sodium 2-chloropropionate, and sodium 3-chloropropionate are preferred from the standpoint of efficiency of introducing substituents, and therefore defibration efficiency, cost, and ease of handling. Furthermore, as an optional component, it is also preferable to use compound B in the above-mentioned <Phosphorus oxo acid group introduction step> in the same manner, and the amount added is also preferably as described above.
[0095] Compound E C When adding, it may be added to the fiber raw material as a reagent (solid or liquid) as it is, or may be dissolved in a suitable solvent and added. It is preferable that the fiber raw material is converted into alkali cellulose in advance or simultaneously with the reaction. The method of conversion into alkali cellulose is as described above.
[0096] The reaction temperature is, for example, preferably 50°C or more and 300°C or less, more preferably 100°C or more and 250°C or less, and further preferably 130°C or more and 200°C or less.
[0097] Compound E CThe amount of addition per 100 parts by mass of the fiber raw material is preferably 1 part by mass to 100,000 parts by mass, more preferably 2 parts by mass to 10,000 parts by mass, and even more preferably 5 parts by mass to 1,000 parts by mass.
[0098] The reaction time may vary depending on the reaction temperature, but is, for example, preferably from 1 minute to 1,000 minutes, more preferably from 3 minutes to 500 minutes, and further preferably from 5 minutes to 400 minutes. After the reaction, excess reaction reagents, by-products, etc. may be washed with water and removed by filtration or the like.
[0099] <Cationic group introduction step (cationization step)> As an essential component, a compound having a reactive group and a cationic group (compound E D ), an optional alkaline compound, and compound B selected from the above-mentioned urea and its derivatives are added to a wet or dry fiber raw material having a hydroxyl group and reacted to introduce a cationic group into the fiber raw material.
[0100] Examples of the reactive group include a halogenated alkyl group, a vinyl group, and an epoxy group (glycidyl group). Examples of the cationic group include an ammonium group, a phosphonium group, a sulfonium group, etc. Among these, the cationic group is preferably an ammonium group. Compound E D As the alkyl group, glycidyl trimethyl ammonium chloride, 3-chloro-2-hydroxypropyl trimethyl ammonium chloride, etc. are preferred from the viewpoints of the efficiency of introducing a substituent, and therefore the defibration efficiency, cost, and ease of handling. Furthermore, as an optional component, it is also preferable to use the compound B in the above-mentioned <Phosphorus oxo acid group introduction step> in the same manner. The amount of addition is also preferably as described above.
[0101] Compound E DWhen adding, it may be added to the fiber raw material as a reagent (solid or liquid) as it is, or may be dissolved in a suitable solvent and added. It is preferable that the fiber raw material is converted into alkali cellulose in advance or simultaneously with the reaction. The method of conversion into alkali cellulose is as described above.
[0102] The reaction temperature is, for example, preferably 50°C or more and 300°C or less, more preferably 100°C or more and 250°C or less, and further preferably 130°C or more and 200°C or less.
[0103] Compound E D The amount of addition per 100 parts by mass of the fiber raw material is preferably 1 part by mass to 100,000 parts by mass, more preferably 2 parts by mass to 10,000 parts by mass, and even more preferably 5 parts by mass to 1,000 parts by mass.
[0104] The reaction time may vary depending on the reaction temperature, but is, for example, preferably from 1 minute to 1,000 minutes, more preferably from 5 minutes to 500 minutes, and further preferably from 10 minutes to 400 minutes. After the reaction, excess reaction reagents, by-products, etc. may be washed and removed with water by filtration or the like.
[0105] <Cleaning process> In the process of obtaining cellulose fibers having ionic substituents, a washing step can be carried out on the fibers having ionic substituents introduced therein, if necessary. The washing step is carried out, for example, by washing the fibers having ionic substituents introduced therein with water or an organic solvent. The washing step may be carried out after each step described below, and the number of washing steps carried out in each washing step is not particularly limited.
[0106] <Alkaline treatment process> In the process for obtaining cellulose fibers having an ionic substituent, an alkali treatment process may be provided between the ionic substituent introduction process and the microfine treatment process. The alkali treatment method is not particularly limited, but may be, for example, a method of immersing the ionic substituent-introduced fibers in an alkali solution.
[0107] The alkaline compound contained in the alkaline solution is not particularly limited, and may be an inorganic alkaline compound or an organic alkaline compound. In this embodiment, it is preferable to use, for example, sodium hydroxide or potassium hydroxide as the alkaline compound because of its high versatility. The solvent contained in the alkaline solution may be either water or an organic solvent. Among them, the solvent contained in the alkaline solution is preferably a polar solvent including water or a polar organic solvent exemplified by alcohol, and more preferably an aqueous solvent including at least water. As the alkaline solution, for example, an aqueous sodium hydroxide solution or an aqueous potassium hydroxide solution is preferable because of its high versatility.
[0108] The temperature of the alkaline solution in the alkaline treatment step is not particularly limited, but is preferably from 5° C. to 80° C., more preferably from 10° C. to 60° C. The time for immersing the ionic substituent-introduced fiber in the alkaline solution in the alkaline treatment step is not particularly limited, but is preferably from 5 minutes to 30 minutes, more preferably from 10 minutes to 20 minutes. The amount of the alkaline solution used in the alkaline treatment is not particularly limited, but is preferably from 100 mass% to 100,000 mass%, more preferably from 1,000 mass% to 10,000 mass%, based on the absolute dry mass of the ionic substituent-introduced fiber.
[0109] In order to reduce the amount of alkaline solution used in the alkaline treatment step, the ionic substituent-introduced fiber may be washed with water or an organic solvent after the ionic substituent-introducing step and before the alkaline treatment step. From the viewpoint of improving the handleability, it is preferable to wash the ionic substituent-introduced fiber that has been subjected to the alkaline treatment with water or an organic solvent after the alkaline treatment step and before the microparticulation treatment step.
[0110] <Acid treatment process> In the process for obtaining cellulose fibers having an ionic substituent, an acid treatment process may be provided between the ionic substituent introduction process and the microfibrillation process. For example, the ionic substituent introduction process, acid treatment, alkali treatment and microfibrillation process may be carried out in this order.
[0111] The method of acid treatment is not particularly limited, but for example, a method of immersing the fiber raw material in an acidic solution containing an acid can be mentioned. The concentration of the acidic solution used is not particularly limited, but for example, preferably 10% by mass or less, more preferably 5% by mass or less. The pH of the acidic solution used is not particularly limited, but for example, preferably 0 to 4, more preferably 1 to 3. The acid contained in the acidic solution can be, for example, an inorganic acid, a sulfonic acid, a carboxylic acid, etc. Examples of the inorganic acid include sulfuric acid, nitric acid, hydrobromic acid, hydroiodic acid, hypochlorous acid, chlorous acid, chloric acid, perchloric acid, phosphoric acid, boric acid, etc. Examples of the sulfonic acid include methanesulfonic acid, ethanesulfonic acid, benzenesulfonic acid, p-toluenesulfonic acid, trifluoromethanesulfonic acid, etc. Examples of the carboxylic acid include formic acid, acetic acid, citric acid, gluconic acid, lactic acid, oxalic acid, tartaric acid, etc. Among these, it is particularly preferable to use hydrochloric acid or sulfuric acid.
[0112] The temperature of the acid solution in the acid treatment is not particularly limited, but is preferably from 5° C. to 100° C., more preferably from 20° C. to 90° C., for example. The immersion time in the acid solution in the acid treatment is not particularly limited, but is preferably from 5 minutes to 120 minutes, more preferably from 10 minutes to 60 minutes, for example. The amount of the acid solution used in the acid treatment is not particularly limited, but is preferably from 100 mass% to 100,000 mass%, more preferably from 1,000 mass% to 10,000 mass%, for example, based on the absolute dry mass of the fiber raw material.
[0113] <<Fiber-defibrating process>> By subjecting the fiber raw material or the ionic group-introduced fiber to defibration processing in a defibration processing step, fine fibrous cellulose can be obtained. Defibration processing is also called fine processing. In the defibration processing step, for example, a defibration processing device can be used. The defibration processing device is not particularly limited, but for example, a high-speed defibrator, a grinder (stone mill type grinder), a high-pressure homogenizer or an ultra-high-pressure homogenizer, a high-pressure collision type grinder, a ball mill, a bead mill, a disk type refiner, a conical refiner, a biaxial kneader, a vibration mill, a homomixer under high-speed rotation, an ultrasonic disperser, or a beater can be used. Among the above defibration processing devices, it is more preferable to use a high-speed defibrator, a high-pressure homogenizer, or an ultra-high-pressure homogenizer, which are less affected by the grinding media and have less risk of contamination.
[0114] In the defibration process, for example, the fiber raw material or the ionic group-introduced fiber is preferably diluted with a dispersion medium to form a slurry. As the dispersion medium, one or more selected from water and organic solvents such as polar organic solvents can be used. The polar organic solvent is not particularly limited, but for example, alcohols, polyhydric alcohols, ketones, ethers, esters, aprotic polar solvents, etc. are preferable. Examples of alcohols include methanol, ethanol, isopropanol, n-butanol, isobutyl alcohol, etc. Examples of polyhydric alcohols include ethylene glycol, propylene glycol, glycerin, etc. Examples of ketones include acetone, methyl ethyl ketone (MEK), etc. Examples of ethers include diethyl ether, tetrahydrofuran, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol mono n-butyl ether, propylene glycol monomethyl ether, etc. Examples of esters include ethyl acetate, butyl acetate, etc. Aprotic polar solvents include dimethylsulfoxide (DMSO), dimethylformamide (DMF), dimethylacetamide (DMAc), and N-methyl-2-pyrrolidinone (NMP).
[0115] The solid content concentration of the fine fibrous cellulose during the defibration treatment can be appropriately set. In addition, the slurry obtained by dispersing the ionic group-introduced fibers in a dispersion medium may contain solid contents other than the ionic group-introduced fibers, such as urea having hydrogen bonding properties.
[0116] <Substituent Removal Treatment> The method for producing fine fibrous cellulose may include a substituent removal treatment step of removing at least a part of the substituent from fine fibrous cellulose having a substituent and having a fiber width of 1000 nm or less. In this specification, the step of removing at least a part of the substituent from the fine fibrous cellulose obtained by the above-mentioned step is also referred to as a substituent removal treatment step.
[0117] Examples of the substituent removal treatment step include a step of heat treating, enzyme treating, acid treating, alkali treating, etc., fine fibrous cellulose having a substituent and a fiber width of 1000 nm or less. These may be performed alone or in combination. Among them, the substituent removal treatment step is preferably a heat treating step or an enzyme treating step. By going through the above treatment steps, at least a portion of the substituents can be removed from fine fibrous cellulose having a substituent and a fiber width of 1000 nm or less, and fine fibrous cellulose with an introduction amount of less than 0.5 mmol / g can be obtained.
[0118] The substituent removal treatment step is preferably carried out in the form of a slurry. That is, the substituent removal treatment step is preferably a step of subjecting a slurry containing a fine fibrous cellulose having a substituent and a fiber width of 1000 nm or less to a heat treatment, an enzyme treatment, an acid treatment, an alkali treatment, or the like. By carrying out the substituent removal treatment step in the form of a slurry, it is possible to prevent the residue of colored substances generated by heating or the like during the substituent removal treatment, and acids, alkalis, salts, etc. that are added or generated. This makes it possible to suppress coloration of the fine fibrous cellulose. In addition, when a treatment is carried out to remove salts derived from the substituents removed after the substituent removal treatment, it is also possible to increase the efficiency of salt removal.
[0119] When a substitution removal treatment is performed on a slurry containing a fine fibrous cellulose having a substituent and a fiber width of 1000 nm or less, the concentration of the fine fibrous cellulose in the slurry is preferably 0.05% by mass or more and 20% by mass or less, more preferably 0.1% by mass or more, even more preferably 0.2% by mass or more, and more preferably 15% by mass or less, and even more preferably 10% by mass or less. By setting the concentration of the fine fibrous cellulose in the slurry within the above range, the substitution removal treatment can be performed more efficiently. Furthermore, by setting the concentration of the fine fibrous cellulose in the slurry within the above range, it is possible to prevent the residue of colored substances generated by heating during the substitution removal treatment, and acids, alkalis, salts, etc. that are added or generated. This makes it possible to suppress coloring of the obtained fine fibrous cellulose. In addition, when a treatment is performed to remove salts derived from the substituents removed after the substitution removal treatment, it is also possible to increase the efficiency of salt removal.
[0120] When the substituent removal treatment step is a step of heat-treating fine fibrous cellulose having a substituent and a fiber width of 1000 nm or less, the heating temperature in the heat treatment step is preferably 40° C. or more and 250° C. or less, more preferably 50° C. or more, even more preferably 60° C. or more, more preferably 230° C. or less, and even more preferably 200° C. or less. In particular, when the substituent of the fine fibrous cellulose to be subjected to the substituent removal treatment step is a phosphorus oxoacid group or a sulfone group, the heating temperature in the heat treatment step is preferably 80° C. or more, more preferably 100° C. or more, and even more preferably 120° C. or more.
[0121] When the substituent removal treatment step is a step of heat treatment, the heating device that can be used in the heat treatment step is not particularly limited, but a hot air heating device, a steam heating device, an electric heating device, a hydrothermal heating device, a thermal heating device, an infrared heating device, a far-infrared heating device, a microwave heating device, a high-frequency heating device, a stirring dryer, a rotary dryer, a disk dryer, a roll-type heating device, a plate-type heating device, a fluidized bed dryer, a band-type dryer, a filtration dryer, a vibration fluidized dryer, an airflow dryer, and a reduced pressure dryer can be used. From the viewpoint of preventing evaporation, it is preferable that the heating is performed in a closed system, and from the viewpoint of further increasing the heating temperature, it is preferable that the heating is performed in a pressure-resistant device or container. The heating treatment may be a batch treatment, a batch continuous treatment, or a continuous treatment.
[0122] When the substituent removal treatment step is a step of enzymatically treating fine fibrous cellulose having substituents and a fiber width of 1000 nm or less, it is preferable to use a phosphate ester hydrolase, a sulfate ester hydrolase, or the like in the enzymatic treatment step. In the enzyme treatment step, the enzyme is preferably added so that the enzyme activity per 1 g of fine fibrous cellulose is 0.1 nkat or more and 100,000 nkat or less, more preferably 1.0 nkat or more, even more preferably 10 nkat or more, and even more preferably 50,000 nkat or less, even more preferably 10,000 nkat or less. After the enzyme is added to the fine fibrous cellulose dispersion (slurry), it is preferable to carry out a treatment under conditions of 0°C or more and less than 50°C for 1 minute to 100 hours.
[0123] After the enzyme reaction, a step of inactivating the enzyme may be performed. Examples of the method of inactivating the enzyme include a method of inactivating the enzyme by adding an acid component or an alkali component to the slurry that has been subjected to the enzyme treatment, and a method of inactivating the enzyme by raising the temperature of the slurry that has been subjected to the enzyme treatment to 90° C. or higher.
[0124] When the substituent removal treatment step is a step of acid-treating fine fibrous cellulose having a substituent and a fiber width of 1000 nm or less, it is preferable to add an acid compound that can be used in the acid treatment step described above to the slurry in the acid treatment step.
[0125] When the substituent removal treatment step is a step of subjecting fine fibrous cellulose having a substituent and having a fiber width of 1000 nm or less to an alkali treatment, it is preferable to add an alkali compound that can be used in the alkali treatment step described above to the slurry in the alkali treatment step.
[0126] In the substituent removal treatment step, it is preferable that the substituent removal reaction proceeds uniformly. In order to proceed with the reaction uniformly, for example, the slurry containing the fine fibrous cellulose may be stirred, or the specific surface area of the slurry may be increased. As a method for stirring the slurry, an external mechanical shear may be applied, or the self-stirring may be promoted by increasing the liquid feed rate of the slurry during the reaction.
[0127] In the substituent removal treatment step, a spacer molecule may be added. The spacer molecule enters between adjacent fine fibrous cellulose particles, thereby acting as a spacer for providing a fine space between the fine fibrous cellulose particles. By adding such a spacer molecule in the substituent removal treatment step, it is possible to suppress the aggregation of the fine fibrous cellulose after the substituent removal treatment. This makes it possible to more effectively improve the design and tensile properties of a rubber composition, a crosslinked rubber composition, and a crosslinked rubber product containing the fine fibrous cellulose.
[0128] The spacer molecule is preferably a water-soluble organic compound. Examples of the water-soluble organic compound include sugar, water-soluble polymer, and urea. Specific examples include trehalose, urea, polyethylene glycol (PEG), polyethylene oxide (PEO), carboxymethyl cellulose, and polyvinyl alcohol (PVA). In addition, water-soluble organic compounds that can be used include alkyl methacrylate-acrylic acid copolymers, polyvinylpyrrolidone, sodium polyacrylate, propylene glycol, dipropylene glycol, polypropylene glycol, isoprene glycol, hexylene glycol, 1,3-butylene glycol, polyacrylamide, xanthan gum, guar gum, tamarind gum, carrageenan, locust bean gum, quince seed, alginic acid, pullulan, carrageenan, pectin, cationic starch, raw starch, oxidized starch, etherified starch, esterified starch, amylose and other starches, glycerin, diglycerin, polyglycerin, hyaluronic acid, and metal salts of hyaluronic acid.
[0129] Also, known pigments can be used as spacer molecules, such as kaolin (containing clay), calcium carbonate, titanium oxide, zinc oxide, amorphous silica (containing colloidal silica), aluminum oxide, zeolite, sepiolite, smectite, synthetic smectite, magnesium silicate, magnesium carbonate, magnesium oxide, diatomaceous earth, styrene-based plastic pigments, hydrotalcite, urea resin-based plastic pigments, and benzoguanamine-based plastic pigments.
[0130] 《pH adjustment process》 When the substituent removal treatment step is carried out in the form of a slurry, a step of adjusting the pH of the slurry containing the fine fibrous cellulose may be provided prior to the substituent removal treatment step. For example, an anionic group is introduced into the cellulose fiber, and the counter ion of the anionic group is Na +In this case, the slurry containing the defibrated fine fibrous cellulose exhibits weak alkalinity. When heating is performed in this state, monosaccharides, which are one of the causes of coloring, may be generated due to decomposition of the cellulose, so the pH of the slurry is preferably adjusted to 8 or less, and more preferably adjusted to 6 or less. Similarly, monosaccharides may be generated under acidic conditions, so the pH of the slurry is preferably adjusted to 3 or more, and more preferably adjusted to 4 or more.
[0131] In addition, when the fine fibrous cellulose having a substituent is a fine fibrous cellulose having a phosphate group, from the viewpoint of improving the efficiency of removing the substituent, it is preferable that the phosphorus of the phosphate group is in a state that is easily susceptible to nucleophilic attack. - H + )(-O - Na + To achieve this state, the pH of the slurry is adjusted to preferably 3 or more and 8 or less, more preferably 4 or more and 6 or less.
[0132] The means for adjusting the pH is not particularly limited, and for example, an acid component or an alkali component may be added to the slurry containing the fine fibrous cellulose. The acid component may be either an inorganic acid or an organic acid, and examples of the inorganic acid include sulfuric acid, hydrochloric acid, nitric acid, and phosphoric acid. Examples of the organic acid include formic acid, acetic acid, citric acid, malic acid, lactic acid, adipic acid, sebacic acid, stearic acid, maleic acid, succinic acid, tartaric acid, fumaric acid, and gluconic acid. The alkali component may be an inorganic alkali compound or an organic alkali compound. Examples of the inorganic alkali compound include lithium hydroxide, sodium hydroxide, potassium hydroxide, lithium carbonate, lithium hydrogen carbonate, potassium carbonate, potassium hydrogen carbonate, sodium carbonate, and sodium hydrogen carbonate. Examples of the organic alkali compound include ammonia, hydrazine, methylamine, ethylamine, diethylamine, triethylamine, propylamine, dipropylamine, butylamine, diaminoethane, diaminopropane, diaminobutane, diaminopentane, diaminohexane, cyclohexylamine, aniline, tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetrabutylammonium hydroxide, benzyltrimethylammonium hydroxide, pyridine, and N,N-dimethyl-4-aminopyridine.
[0133] In addition, in the pH adjustment step, an ion exchange treatment may be performed to adjust the pH. In the ion exchange treatment, a strong acid cation exchange resin or a weak acid ion exchange resin may be used. By treating with an appropriate amount of cation exchange resin for a sufficient time, a slurry containing fine fibrous cellulose with a desired pH can be obtained. Furthermore, in the pH adjustment step, the addition of an acid component or an alkali component may be combined with the ion exchange treatment.
[0134] Salt removal process After the substituent removal treatment step, it is preferable to perform a treatment for removing salts derived from the removed substituents. By removing the salts derived from the substituents, it becomes easier to obtain fine fibrous cellulose capable of suppressing coloration. The means for removing the salts derived from the substituents is not particularly limited, and examples thereof include a washing treatment. The washing treatment is performed, for example, by washing the fine fibrous cellulose aggregated in the substituent removal treatment with water or an organic solvent. From the viewpoint of more effectively suppressing yellowing, the washing treatment is preferably performed by filtration dehydration, centrifugal dehydration, or centrifugation.
[0135] <Uniform distribution processing> The method for producing fine fibrous cellulose may include a substituent removal treatment step of removing at least a part of the substituent from fine fibrous cellulose having a substituent and a fiber width of 1000 nm or less, and a uniform dispersion treatment step after the substituent removal treatment. The uniform dispersion treatment step is a step of uniformly dispersing the fine fibrous cellulose obtained through the substituent removal treatment in the substituent removal treatment step. The state in which the fine fibrous cellulose is uniformly dispersed in the uniform dispersion treatment step refers to a state in which the fiber width of the fine fibrous cellulose is 100 nm or less. By undergoing the uniform dispersion treatment step, the fine fibrous cellulose can easily have a number average fiber width of 100 nm or less, preferably 50 nm or less, even though the amount of substituents introduced is a low amount of less than 0.5 mmol / g.
[0136] In the uniform dispersion process, for example, a high-speed defibrator, a grinder (stone mill type grinder), a high-pressure homogenizer, a high-pressure collision type grinder, a ball mill, a bead mill, a disk type refiner, a conical refiner, a twin-shaft kneader, a vibration mill, a homomixer under high-speed rotation, an ultrasonic disperser or a beater can be used. Among the above uniform dispersion treatment devices, it is more preferable to use a high-speed defibrator or a high-pressure homogenizer.
[0137] The treatment conditions in the uniform dispersion process are not particularly limited, but it is preferable to increase the maximum movement speed of the fine fibrous cellulose during treatment and the pressure during treatment. In the case of a high-speed defibrator, the peripheral speed is preferably 20 m / sec or more, more preferably 25 m / sec or more, and even more preferably 30 m / sec or more. A high-pressure homogenizer is more preferably used because it has a higher maximum movement speed of the fine fibrous cellulose during treatment and a higher pressure during treatment than a high-speed defibrator. In the high-pressure homogenizer treatment, the pressure during treatment is preferably 1 MPa or more to 350 MPa, more preferably 10 MPa or more, even more preferably 50 MPa or more, even more preferably 100 MPa or more, and more preferably 300 MPa or less, and even more preferably 250 MPa or less.
[0138] In the uniform dispersion treatment step, the above-mentioned spacer molecule may be added. By adding such a spacer molecule in the uniform dispersion treatment step, the fine fibrous cellulose can be more smoothly dispersed uniformly.
[0139] <Coarse cellulose fibers> In this embodiment, the fibrous cellulose may contain coarse cellulose fibers having a fiber width exceeding 1 μm, and when the fibrous cellulose contains coarse cellulose fibers, it is preferable that the fibrous cellulose contains fine fibrous cellulose having a fiber width of 1000 nm or less in addition to the coarse cellulose fibers. The fiber width of the coarse cellulose fibers is not particularly limited as long as it is 1 μm or more, but is, for example, preferably 1 μm or more and 100 μm or less, more preferably 5 μm or more, even more preferably 10 μm or more, and more preferably 50 μm or less, even more preferably 40 μm or less. The fiber width of the coarse cellulose fibers can be determined by a fiber length distribution measuring device (for example, FS5 manufactured by Valmet, L&W Fiber Tester Plus manufactured by ABB).
[0140] From the viewpoint of improving dispersibility in the rubber composition, the coarse cellulose fibers preferably have an ionic substituent, and the preferred embodiments of the ionic substituent are the same as those of the fine fibrous cellulose, and the preferred ranges of the type and amount of the substituent are also the same. The coarse cellulose fibers are preferably obtained by introducing ionic groups into a fiber raw material and then gently defibrating the raw material. Examples of defibrators used for the gentle defibration treatment include refiners such as disk refiners and conical refiners.
[0141] When the fibrous cellulose contains coarse cellulose fibers, the content of the coarse cellulose fibers per 100 parts by mass of the combined total of the fine fibrous cellulose and the coarse cellulose fibers is preferably 1 part by mass or more and 95 parts by mass or less, more preferably 3 parts by mass or more, even more preferably 5 parts by mass or more, and is preferably 90 parts by mass or less, more preferably 85 parts by mass or less. When the content of coarse cellulose fibers is within the above range, the coarse cellulose fibers can be produced more cheaply than fine fibrous cellulose, and therefore the rubber composition can be produced more cheaply, and a rubber composition having excellent kneadability and excellent physical properties after crosslinking can be obtained, which is preferable.
[0142] The solid rubber composition of the present embodiment may contain, in addition to the rubber component and fibrous cellulose, other components such as zinc oxide, a crosslinking promoter, an antioxidant, a reinforcing agent, and the like, which may be added at any step in the production process.
[0143] (Step of Preparing Solid Rubber Composition) <Production of rubber mixture> Although the method for preparing the solid rubber composition is not particularly limited, it is preferable to prepare (manufacture) a rubber mixture by preparing a dispersion containing at least a rubber component and fibrous cellulose and removing the dispersion medium from the dispersion. The rubber mixture is preferably in the form of a sheet. In the above-mentioned production method, it is preferable to first mix the fibrous cellulose and the rubber component to prepare a dispersion of the mixture in an aqueous medium (hereinafter, also simply referred to as a "dispersion of the mixture").
[0144] Specifically, fibrous cellulose and a rubber component are mixed and dispersed in an aqueous medium to obtain a dispersion of the mixture. Alternatively, an aqueous dispersion of fibrous cellulose and an aqueous dispersion of a rubber component can be mixed to obtain a dispersion of the mixture. Among these, it is preferable to mix a dispersion of fibrous cellulose and an aqueous dispersion of a rubber component to obtain a dispersion containing fibrous cellulose and a rubber component. An example of an aqueous dispersion of a rubber component is rubber latex. That is, the process of preparing a solid rubber composition preferably includes a step of mixing a latex containing a rubber component with an aqueous dispersion containing fibrous cellulose to obtain a mixed liquid, and a step of drying the mixed liquid. When the solid rubber composition is a rubber mixture, the process of preparing a solid rubber composition preferably includes a step of mixing a latex containing a rubber component with an aqueous dispersion containing fibrous cellulose to obtain a mixed liquid, and a step of drying the mixed liquid. The mixing can be carried out using a known device such as a disperser, a three-one motor, a clear mix, a homomixer, a homogenizer, a propeller stirrer, etc. The mixing temperature is not limited, but room temperature (20 to 30° C.) is preferable. The mixing time can also be appropriately adjusted. When preparing the dispersion of the mixture, it is preferable to thoroughly mix the fibrous cellulose and the rubber component.
[0145] The rubber latex is preferably a dispersion of a rubber component in an aqueous medium. The aqueous medium is mainly composed of water, and the content of water in the entire aqueous medium is preferably 50% by mass or more, more preferably 80% by mass or more, even more preferably 90% by mass or more, and even more preferably 95% by mass or more, and the upper limit is not particularly limited, but is 100% by mass or less. In addition to water, the aqueous medium may contain a known organic solvent, etc., to the extent that the effect of the present disclosure is not impaired.
[0146] The solid content concentration (mass basis) of the mixture dispersion is preferably 0.5 mass % or more and 50 mass % or less, more preferably 1 mass % or more, even more preferably 3 mass % or more, and more preferably 40 mass % or less, and even more preferably 30 mass % or less. When the solid content concentration of the mixture dispersion is within the above range, the amount of energy required to remove water can be reduced, and further, aggregation of the fine fibrous cellulose is less likely to occur in the obtained rubber composition, resulting in excellent kneadability of the obtained rubber composition and excellent properties of the crosslinked product.
[0147] The rubber mixture may be obtained by heating and drying a dispersion of the obtained mixture. The heat drying method is not particularly limited, and examples thereof include a method of coating a dispersion of the mixture on a substrate, and a method of drying with a drum dryer. In the coating method, for example, a dispersion of a mixture containing a rubber component and fibrous cellulose is coated on a substrate. When the solid rubber composition is a rubber mixture, a coating device and a long substrate can be used to continuously produce a sheet-like rubber mixture. The material of the substrate used in the coating method is not particularly limited, but when the solid rubber composition is a rubber mixture, a substrate having a high wettability with respect to the dispersion liquid of the mixture can suppress the shrinkage of the rubber mixture during drying, but it is preferable to select a substrate from which the sheet-like rubber mixture formed after drying can be easily peeled off. Among them, a resin film or plate or a metal film or plate is preferable, but is not particularly limited. For example, a resin film or plate such as acrylic, polyethylene terephthalate, vinyl chloride, polystyrene, polypropylene, polycarbonate, polyvinylidene chloride, etc., a metal film or plate such as aluminum, zinc, copper, or iron plate, and those whose surfaces have been oxidized, a stainless steel film or plate, a brass film or plate, etc. can be used. In the coating method, when the viscosity of the dispersion of the mixture is low and it spreads on the substrate, and the solid rubber composition is a sheet-shaped rubber mixture, a damming frame may be fixed on the substrate to obtain a sheet-shaped rubber mixture of a predetermined thickness and basis weight. A substrate with a batt-shaped damming may also be used. The damming frame is not particularly limited, but it is preferable to select one that allows the end of the sheet-shaped rubber mixture to be easily peeled off after drying. From this perspective, a molded resin plate or metal plate is more preferable. In this embodiment, for example, resin plates such as acrylic plates, polyethylene terephthalate plates, vinyl chloride plates, polystyrene plates, polypropylene plates, polycarbonate plates, and polyvinylidene chloride plates, metal plates such as aluminum plates, zinc plates, copper plates, and iron plates, and those whose surfaces have been oxidized, and molded stainless steel plates, brass plates, and the like can be used. The coater for applying the dispersion of the mixture to the substrate is not particularly limited, and examples thereof include a roll coater, a gravure coater, a die coater, a curtain coater, an air doctor coater, etc. When the solid rubber composition is a rubber mixture in a sheet form, a die coater, a curtain coater, and a spray coater are particularly preferred since they can make the thickness of the sheet more uniform.
[0148] The temperature of the dispersion liquid of the mixture and the ambient temperature when the dispersion liquid of the mixture is applied to the substrate (hereinafter, the dispersion liquid temperature of the mixture and the ambient temperature are collectively referred to as "coating temperature") are not particularly limited, but are preferably, for example, from 5°C to 80°C, more preferably from 10°C to 60°C, even more preferably from 15°C to 50°C, and particularly preferably from 20°C to 50°C. If the coating temperature is equal to or higher than the lower limit, the dispersion liquid of the mixture can be more easily applied. If the coating temperature is equal to or lower than the upper limit, the volatilization of the dispersion medium during coating can be suppressed. The drying device to be used is not particularly limited, but an explosion-proof dryer is an example. When the solid rubber composition is a sheet-like rubber mixture, in the coating step, it is preferable to coat a dispersion of the mixture onto a substrate so that the finished basis weight and thickness fall within the above-mentioned preferred ranges.
[0149] The mixture dispersion may be heated and dried using a cylindrical heater to obtain a rubber mixture. FIG. 3 is a schematic cross-sectional side view of a double drum dryer 10 which is an example of a heating cylindrical dryer, and FIG. First, a heat medium (generally steam) is fed into the rotating cylinder 1 (drum), and a mixture dispersion is fed into the feed section 2. The fed mixture dispersion adheres to the surface of the heated cylinder 1 as a sheet-like mixture 3, which is promptly dried by heating. As the cylinder 1 rotates, the sheet-like mixture 3 is scraped off by a fixed scraper 4, and a rubber mixture 5 (heat-dried material) can be obtained.
[0150] The lower limit of the surface temperature of the heating cylindrical dryer is preferably 80° C. or higher, and more preferably 90° C. or higher. The upper limit of the surface temperature is preferably 250° C. or lower, and more preferably 200° C. or lower. The surface temperature of the heated cylindrical dryer refers to the temperature of the cylindrical surface with which the mixture comes into contact. The surface temperature of the heated cylindrical dryer may be, for example, 80 to 250° C., 90 to 200° C., or 95 to 180° C. When the surface temperature of the heated cylindrical dryer is within the above range, a sheet-shaped rubber mixture having good production efficiency, excellent kneadability, and excellent physical properties after crosslinking can be obtained.
[0151] The lower limit of the time for drying by heating in a heating cylindrical dryer is preferably 2 seconds or more, more preferably 4 seconds or more, and the upper limit of the time for drying by heating is preferably 1800 seconds or less, more preferably 600 seconds or less. The time [sec] for drying by heating in a heating cylinder dryer refers to the time [sec] for which the mixture is in contact with the surface of the cylinder, and the time for drying by heating may be, for example, 2 to 1800 seconds, 4 to 600 seconds, or 6 to 400 seconds. By keeping the time for drying by heating within the above range, a dried product that is neither underdried nor overdried can be obtained, and the peelability from the drum is excellent.
[0152] The lower limit of the cylinder width w of the heating cylinder dryer is preferably 0.1 m or more, more preferably 0.2 m or more. The upper limit of the cylinder width w is not particularly limited, but is usually 7 m or less. The cylinder width w may be, for example, 0.1 to 7 m, or 0.2 to 5 m. When the cylinder width w is within the above range, a dried product with a uniform thickness can be obtained.
[0153] The lower limit of the cylinder rotation speed v of the heating cylinder dryer is preferably 0.001 [m / sec] or more, more preferably 0.002 [m / sec]. The upper limit of the cylinder rotation speed v is not particularly limited, but is usually 35 [m / sec] or less. The cylinder rotation speed v may be, for example, 0.001 to 3.5 [m / sec], or 0.002 to 0.2 [m / sec]. By setting the cylinder rotation speed v within the above range, the time during which the mixture contacts the heated drum can be set to an appropriate range, and a dried product having excellent kneadability and physical properties after crosslinking can be obtained.
[0154] The heated cylindrical dryer used in the production of the rubber mixture may be a conductive heating type dryer in which a heat medium is introduced into the inside of a cylinder and the mixture is brought into contact with the surface of the heated cylinder to perform heat drying. For example, a drum dryer such as a double drum dryer, a single drum dryer, or a twin drum dryer may be used, and a cylinder dryer, a Yankee dryer, or the like may also be used. Among these, from the viewpoint of heat drying efficiency, the heated cylindrical dryer is preferably a double drum dryer or a cylinder dryer.
[0155] <Production of masticated rubber composition> The rubber mixture obtained as described above is masticated to obtain a masticated rubber composition. In other words, the process for preparing a solid rubber composition preferably includes, in this order, a step of mixing a latex containing a rubber component with an aqueous dispersion containing fibrous cellulose to obtain a mixed liquid, a step of drying the mixed liquid, and a step of masticating the obtained dried product. The mastication may be carried out by a conventional method, and may be low-temperature kneading using a roll machine such as an open roll, or high-temperature kneading using a Banbury mixer. Among these, low-temperature kneading is preferable from the viewpoint of dispersibility of fibrous cellulose in the solid rubber composition. The temperature of low-temperature kneading is preferably 15°C or more and 70°C or less, more preferably 20°C or more and 65°C or less, and even more preferably 25°C or more and 60°C or less. The temperature of high-temperature kneading is preferably 80°C or more and 200°C or less.
[0156] <Production of rubber kneaded product> When the solid rubber composition is a rubber mixture, it is preferable that the process for preparing the solid rubber composition includes, in this order, a process of mixing a latex containing a rubber component with an aqueous dispersion containing fibrous cellulose to obtain a mixed liquid, a process of drying the mixed liquid, a process of masticating the obtained dried product, and a process of adding the rubber component to the masticated dried product and kneading them. That is, the rubber kneaded product is obtained by adding a rubber component to a masticated rubber composition and kneading them. The kneading may be carried out in a known manner, for example, by using a Banbury mixer, a kneader, an open roll or the like. The rubber component to be added is the same as the rubber component exemplified above, but it is sufficient to add a solid rubber (solid rubber) instead of adding it in a latex form. The amount to be added is not particularly limited, and may be appropriately adjusted depending on the desired application.
[0157] <Production of Crosslinked Rubber Composition and Crosslinked Rubber Product> The crosslinked rubber composition of the present embodiment is obtained by crosslinking a rubber compound containing a crosslinking agent. In addition, by molding during crosslinking, a crosslinked rubber product can be obtained. That is, the crosslinked rubber product is obtained by crosslinking and molding the rubber compound. <Production of rubber compounds> The method for producing the rubber compound is not particularly limited, but the rubber compound is produced by adding at least a crosslinking agent to a rubber mixture, a masticated rubber composition, or a kneaded rubber composition, and kneading the mixture. In the present embodiment, the rubber compound refers to a composition in a pre-crosslinked state obtained by adding at least a crosslinking agent to a composition containing a rubber component and fibrous cellulose and kneading the mixture. The rubber compound contains at least a crosslinking agent, and may contain, in addition to the crosslinking agent, additives that can be used as additives in the rubber field, such as zinc oxide, vulcanization accelerators, fillers, softeners, fatty acids, antioxidants, peptizers, colorants, pH adjusters, cured resins, etc. In addition, solid rubber may be added when preparing the rubber compound. When solid rubber is newly added, the solid rubber is the same as that exemplified as the rubber component, but it is sufficient to add solid rubber (solid rubber) instead of adding it in the form of latex. Examples of the crosslinking agent include sulfur-based crosslinking agents (e.g., powdered sulfur, sulfur flowers, precipitated sulfur, colloidal sulfur, surface-treated sulfur, insoluble sulfur, and other sulfur; sulfur-containing compounds such as amine disulfide, polymer polysulfide, sulfur olefin adducts, sulfur chloride, and sulfur dichloride; and insoluble polymeric sulfur), peroxide-based crosslinking agents (e.g., dicumyl peroxide, dichlorobenzoyl peroxide, benzoyl peroxide, 1,1-di(t-butylperoxy)-3,3,5-trimethylcyclohexane, n-butyl-4,4-bis(t-butylperoxy)valerate, di-t-butylperoxy-di-isopropylbenzene, and 2,5-dimethyl-2,5-di(t-butylperoxy)hexane), and quinoid-based crosslinking agents (e.g., p-quinone dioxime, p,p'-dibenzoylquinone dioxime), and among these, sulfur-based crosslinking agents or peroxide-based crosslinking agents are preferred. The amount of the crosslinking agent added is not particularly limited, but is preferably 0.1 part by mass or more and 10 parts by mass or less, more preferably 0.5 part by mass or more, even more preferably 1.0 part by mass or less, and is preferably 5 parts by mass or less, more preferably 3 parts by mass or less, relative to 100 parts by mass of the rubber component.
[0158] Furthermore, a crosslinking accelerator having the effect of accelerating crosslinking by a crosslinking agent may be contained, and when a sulfur-based crosslinking agent is used, it is preferable to contain a crosslinking accelerator (vulcanization accelerator). When a sulfur-based crosslinking agent (vulcanizing agent) is used as the crosslinking agent, it is preferable to use a sulfenamide-based vulcanization accelerator, a guanidine-based vulcanization accelerator, a thiazole-based vulcanization accelerator, a thiuram-based vulcanization accelerator, a dithiocarbamate-based vulcanization accelerator, or the like as the crosslinking accelerator (vulcanization accelerator).
[0159] Examples of the filler include carbon black, silica, etc. These fillers may be used alone or in combination of two or more. The content of the filler is not particularly limited, and is preferably 10 parts by mass or more and 150 parts by mass or less, more preferably 20 parts by mass or more and 100 parts by mass or less, based on 100 parts by mass of the rubber component.
[0160] The softener may include aromatic oils, paraffin oils, naphthenic oils, vegetable oils other than castor oil, low PCA oils such as MES, TDAE, SRAE, heavy naphthenic oils, etc. Suitable low PCA oils include various plant-derived oils harvested from vegetables, nuts, and seeds. Plant-derived oils include soybean oil, sunflower oil, safflower oil, corn oil, linseed oil, cottonseed oil, rapeseed oil, cashew oil, sesame oil, camellia oil, jojoba oil, macadamia nut oil, coconut oil, palm oil, etc. The content of the softener, relative to 100 parts by mass of the rubber component, is preferably 1 part by mass or more and 35 parts by mass or less, more preferably 5 parts by mass or more, even more preferably 10 parts by mass or more, and more preferably 30 parts by mass or less, even more preferably 25 parts by mass or less.
[0161] Examples of the fatty acid include stearic acid, palmitic acid, arachidic acid, oleic acid, linoleic acid, arachidonic acid, etc. Among these, stearic acid is preferred. The content of the fatty acid is not particularly limited and is preferably 0.1 part by mass or more and 5 parts by mass or less, and more preferably 1 part by mass or more and 4 parts by mass or less, per 100 parts by mass of the rubber component.
[0162] Examples of the antiaging agent include N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine (6C), 2,2,4-trimethyl-1,2-dihydroquinoline polymer (TMDQ), 6-ethoxy-2,2,4-trimethyl-1,2-dihydroquinoline (AW), N,N'-diphenyl-p-phenylenediamine (DPPD), 2-mercaptobenzimidazole (MBI), etc. The antiaging agent may be used alone or in combination of two or more kinds. The content of the antioxidant is not particularly limited and is preferably 0.1 part by mass or more and 5 parts by mass or less, and more preferably 1 part by mass or more and 3 parts by mass or less, per 100 parts by mass of the rubber component.
[0163] The amount of the zinc oxide (zinc white) is not particularly limited, and is preferably 1 part by mass or more and 10 parts by mass or less, and more preferably 2 parts by mass or more and 8 parts by mass or less, per 100 parts by mass of the rubber component.
[0164] Kneading is a process for uniformly dispersing a crosslinking agent and other compounding agents in a masticated rubber composition or a kneaded rubber composition. Kneading may be carried out in a known manner, for example, using a Banbury mixer, a kneader, an open roll, or the like.
[0165] <Production of crosslinked rubber composition and crosslinked rubber product> The crosslinked rubber composition of the present embodiment is obtained by crosslinking a rubber compound containing a crosslinking agent. In addition, by molding during crosslinking, a crosslinked rubber product can be obtained. That is, the crosslinked rubber product is obtained by crosslinking and molding the rubber compound. In the present invention, the method for producing a crosslinked rubber product may further include a step of molding the rubber compound into an intended shape (molding step). Molding in this molding step can be performed by various molding methods using an extrusion molding machine, a calendar roll, a press, an injection molding machine, a transfer molding machine, a blow molding machine, a foam molding machine, etc. The molding method may be appropriately selected depending on the shape, application, and molding method of the final product. The kneading step and the molding step may be carried out separately or successively.
[0166] Regarding crosslinking, there is no particular restriction on the temperature as long as the crosslinking reaction proceeds under the conditions, but generally, a crosslinked rubber composition is obtained by heating a kneaded rubber compound to crosslink (also called vulcanization when sulfur is contained). The heating temperature is preferably 140°C or higher, preferably 200°C or lower, and more preferably 180°C or lower. Therefore, the heating temperature is preferably about 140 to 200°C, and more preferably about 140 to 180°C. For crosslinking, for example, a vulcanizing device that performs mold vulcanization, can vulcanization, continuous vulcanization, etc. can be used.
[0167] [Water contact step of contacting the solid rubber composition with a liquid containing water] The method for producing a rubber composition according to the present embodiment includes a water contacting step of contacting a solid rubber composition with a liquid containing water. As described above, the solid rubber composition may be a rubber sheet, a masticated rubber composition, a kneaded rubber composition, a rubber compound, a crosslinked rubber composition, or a crosslinked rubber product. The liquid containing water contains water as a solvent and may contain other solvents. The other solvents are preferably water-miscible organic solvents, such as alcohols such as methanol, ethanol, 1-propanol, isopropyl alcohol (IPA), t-butanol, and 1-methoxy-2-propanol (PGME); polyhydric alcohols such as ethylene glycol and glycerin; ketones such as acetone; ethers such as tetrahydrofuran; esters such as ethyl acetate and methyl acetate; amides such as N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone; and sulfoxides such as dimethyl sulfoxide. These may be used alone or in combination of two or more. Among these, alcohols such as ethanol, IPA, and PGME are preferred. The water content in the water-containing liquid is preferably 60% by mass or more, more preferably 80% by mass or more, even more preferably 90% by mass or more, and even more preferably 95% by mass or more, with no particular upper limit, being 100% by mass.
[0168] The water-containing liquid may also be an aqueous solution of an electrolyte or a chelating agent. Examples of electrolytes include compounds that generate metal ions (e.g., sodium (Na) ions, lithium (Li) ions, magnesium (Mg) ions, calcium (Ca) ions, nickel (II) (Ni(II)) ions, cobalt (II) (Co(II)) ions, copper (II) (Cu(II)) ions, manganese (Mn) ions, iron (II) (Fe(II)) ions, vanadium (II) (V(II)) ions, zirconium (Zr) ions, zinc (Zn) ions, aluminum (Al) ions, and iron (III) (Fe(III)) ions), lactate ions, fluoride ions, chloride ions, sulfate ions, nitrate ions, and ammonium ions. The metal ion is preferably a divalent or higher metal ion. The electrolyte that generates the metal ion is preferably a salt derived from a strong acid that is soluble in water. The salt derived from a strong acid refers to a salt derived from a strong acid such as sulfuric acid, hydrochloric acid, or nitric acid. An aqueous solution of the salt exhibits weak to strong acidity. A salt that is highly soluble in water is preferably used, and specific examples of such metal salts include aluminum sulfate, magnesium sulfate, aluminum potassium sulfate, aluminum ammonium sulfate, and ferric chloride sulfate, and aluminum sulfate and magnesium sulfate are preferred. Examples of the chelating agent include ethylenediaminetetraacetic acid (edetic acid), trisodium ethylenediaminetetraacetate (trisodium EDTA), phytic acid, gluconic acid, polyphosphoric acid, and metaphosphoric acid.
[0169] The temperature of the water-containing liquid is not particularly limited, but from the viewpoint of further improving the water resistance of the crosslinked rubber composition obtained from the resulting rubber composition, it is preferably 20°C or higher, more preferably 40°C or higher, even more preferably 60°C or higher, still more preferably 80°C or higher, and even more preferably 85°C or higher. The upper limit is not particularly limited, but from the viewpoint of performing the water contact step at normal pressure, it is preferably 100°C or lower, more preferably 98°C or lower.
[0170] The method for contacting the solid rubber composition with a liquid containing water is not particularly limited, and examples thereof include the following methods. (i) A method of immersing a solid rubber composition in a liquid containing water (ii) A method of spraying (spraying) a liquid containing water onto a solid rubber composition (iii) A method of applying a liquid containing water to the solid rubber composition in the form of running water. The method of contacting the solid rubber composition with the water-containing liquid is not limited to the above-mentioned method. In addition, it is not always necessary to contact the solid rubber composition with an excessive amount of the water-containing liquid, but it is preferable to contact the solid rubber composition with an excessive amount of the water-containing liquid so that impurities in the solid rubber composition are removed.
[0171] [Application] In this embodiment, the obtained crosslinked rubber product can be used for various applications, and is not particularly limited. For example, they are suitable for use in sealing materials, hoses, shoe soles, tire components, anti-vibration rubber, etc. Among these, crosslinked rubber products are suitable for use as tires. EXAMPLES
[0172] The features of the present invention will be described in more detail below with reference to examples and comparative examples. The materials, amounts used, ratios, processing contents, processing procedures, etc. shown in the following examples can be appropriately changed without departing from the spirit of the present invention. Therefore, the scope of the present invention should not be interpreted as being limited by the specific examples shown below.
[0173] <Production Example 1> [Phosphorus oxo-oxidation treatment] The raw pulp used was softwood kraft pulp (solid content 93% by mass, basis weight 245 g / m) manufactured by Oji Paper Co., Ltd. 2 A sheet-like product (with a Canadian Standard Freeness (CSF) of 700 ml when disintegrated and measured in accordance with JIS P 8121-2:2012) was used. This raw pulp was subjected to phosphorus oxo-oxidation treatment as follows. First, a mixed aqueous solution of ammonium dihydrogen phosphate and urea was added to 100 parts by mass (bone dry mass) of the raw pulp to adjust the composition to 45 parts by mass of ammonium dihydrogen phosphate, 120 parts by mass of urea, and 150 parts by mass of water, to obtain a chemical-impregnated pulp. Next, the obtained chemical-impregnated pulp was heated in a hot air dryer at 165°C for 250 seconds to introduce phosphoric acid groups into the cellulose in the pulp, to obtain a phosphorylated pulp. The phosphorylated pulp was then washed. The washing was carried out by repeatedly pouring 10 L of ion-exchanged water into 100 g (bone dry weight) of phosphorylated pulp to obtain a pulp dispersion, stirring the pulp to disperse it uniformly, and then filtering and dehydrating the pulp. The washing was completed when the electrical conductivity of the filtrate became 100 μS / cm or less. Next, the washed phosphorylated pulp was neutralized as follows: First, the washed phosphorylated pulp was diluted with 10 L of ion-exchanged water, and then a 1N aqueous sodium hydroxide solution was added little by little while stirring to obtain a phosphorylated pulp slurry having a pH of 12 to 13. Next, the phosphorylated pulp slurry was dehydrated and washed to obtain a phosphorylated pulp that had been subjected to a neutralization treatment.
[0174] The infrared absorption spectrum of the phosphorylated pulp was measured using FT-IR. -1 Absorption due to the P=O of the phosphate group was observed near the 2θ=14° to 17° position, and it was confirmed that the phosphate group was added to the pulp. In addition, when the obtained phosphorylated pulp was analyzed using an X-ray diffraction device, typical peaks were confirmed at two positions, near 2θ=14° to 17° and near 2θ=22° to 23°, and it was confirmed that it had cellulose type I crystals. The amount of phosphate groups (amount of first dissociated acid) measured by the measurement method described below was 1.45 mmol / g. The total amount of dissociated acid was 2.45 mmol / g.
[0175] Ion-exchanged water was added to the obtained phosphorylated pulp to prepare a slurry with a solid content of 2.2% by mass. This slurry was treated twice with a wet pulverizer (Starburst, manufactured by Sugino Machine Co., Ltd.) at a pressure of 200 MPa to obtain a cellulose nanofiber dispersion liquid containing phosphorylated cellulose nanofibers. The fiber width of the phosphorylated cellulose nanofibers was measured using a transmission electron microscope and found to be 3 to 5 nm.
[0176] X-ray diffraction confirmed that the phosphorylated cellulose nanofibers maintained cellulose type I crystals. The amount of phosphoric acid groups (amount of first dissociated acid groups, strong acid groups) measured by the measurement method described in [Measurement of amount of phosphorus oxoacid groups] below was 1.45 mmol / g. The total amount of dissociated acid was 2.45 mmol / g.
[0177] <Production Example 2> In the phosphorus oxo-oxidation treatment of Production Example 1, the chemical-impregnated pulp was heated in a hot air dryer at 140°C for 200 seconds to obtain phosphorylated pulp. The obtained phosphorylated pulp was subjected to the same washing and neutralization treatment as in Production Example 1 to obtain neutralized phosphorylated pulp. The infrared absorption spectrum of the phosphorylated pulp obtained was measured using FT-IR. As a result, absorption due to the P=O of the phosphoric acid group was observed around 1230 cm-1, and it was confirmed that the phosphoric acid group was added to the pulp. In addition, when the phosphorylated pulp obtained was analyzed using an X-ray diffractometer, typical peaks were confirmed at two positions, around 2θ=14° to 17° and around 2θ=22° to 23°, and it was confirmed that it had cellulose type I crystals. The amount of phosphoric acid groups (amount of first dissociated acid) measured by the measurement method described later was 0.80 mmol / g. The total amount of dissociated acid was 1.40 mmol / g.
[0178] Ion-exchanged water was added to the phosphorylated pulp to prepare a slurry with a solid content of 2.2% by mass. This slurry was processed 12 times with a single-disk refiner with a clearance set to 100 μm to obtain a phosphorylated microfibril cellulose fiber dispersion. The fiber width measured by the measurement method described below was 17.8 μm.
[0179] X-ray diffraction confirmed that the phosphorylated microfibril cellulose fiber maintained cellulose type I crystals. The amount of phosphoric acid groups (amount of first dissociated acid groups, strong acid groups) measured by the measurement method described in [Measurement of amount of phosphorus oxo acid groups] below was 0.80 mmol / g. The total amount of dissociated acid was 1.40 mmol / g.
[0180] <Production Example 3> In Production Example 1, instead of treating twice with a wet atomizer at a pressure of 200 MPa, the mixture was treated 30 times with a single disc refiner with a clearance set to 100 μm, and then treated once with a wet atomizer at a pressure of 150 MPa to obtain a cellulose nanofiber dispersion containing phosphorylated cellulose nanofibers. The fiber width of the phosphorylated cellulose nanofibers was measured using a transmission electron microscope and found to be 3 to 5 nm.
[0181] <Example 1> The cellulose nanofiber dispersion obtained in Production Example 1 was added to a container so that the solid content of the cellulose nanofibers was 100 parts by mass, and then ion-exchanged water was added so that the solid content concentration of the cellulose nanofibers was diluted to 1.0 mass%. A tornado agitator (general-purpose constrained agitator, PM-202, manufactured by AS ONE Corporation) was used as the agitator, and an agitator blade with a diameter of 6 inches was attached. The mixture was stirred at 1000 rpm for 5 minutes to obtain a diluted cellulose nanofiber dispersion.
[0182] [Mixing process] An aqueous dispersion of natural rubber latex (NR) (ULACOL, manufactured by Resitex Co., Ltd.) with a solid content concentration of 61% by mass was added to the resulting 1.0% by mass cellulose nanofiber dispersion so that the solid content of the rubber component was 500 parts by mass. A tornado stirrer was used as the stirrer, and a stirring blade with a diameter of 6 inches was attached, and stirring was carried out at 1000 rpm for 5 minutes to obtain a cellulose nanofiber / natural rubber latex mixture.
[0183] [Drying process] The obtained cellulose nanofiber / natural rubber latex mixture was spread onto a tray with a Teflon (registered trademark) surface treatment so that the thickness after drying would be 0.05 mm, and then dried in an explosion-proof dryer at 40°C for 48 hours to obtain a sheet-like cellulose nanofiber / natural rubber composition.
[0184] [Water contact process] The obtained cellulose nanofiber / natural rubber composition was immersed in ion-exchanged water, sealed, and left to stand for 2 hours in a dryer adjusted to 90°C for hot water treatment. After 2 hours, it was removed from the ion-exchanged water, lightly squeezed to remove the water, spread on a tray, and dried at 40°C for 24 hours to obtain a water-contact-treated cellulose nanofiber / natural rubber composition.
[0185] [Preparation of rubber compound] The obtained water contact treated cellulose nanofiber / natural rubber composition was masticated for 10 minutes without heating at 26 / 30 rpm using an open roll (6-inch two-roll mill, Daihan). Next, 2 parts by mass of a crosslinking agent (Percumil D, NOF Corp.), 3 parts by mass of zinc oxide (zinc oxide type 2, Seido Chemical Industry Co., Ltd.), and 1.5 parts by mass of antioxidants (ANTAGE MB, ANTAGE RD, Kawaguchi Chemical Industry Co., Ltd.) were added to 100 parts by mass of the rubber component, and kneaded for 6 minutes to obtain a rubber compound with a thickness of about 2 mm or more.
[0186] [Crosslinking process] The obtained rubber compound was placed in a mold and press heated at 165° C. for 20 minutes to produce a 2 mm-thick sheet of the crosslinked rubber composition.
[0187] <Example 2> A sheet of a crosslinked rubber composition was obtained by carrying out the same treatment as in Example 1, except that the microfibril cellulose fiber dispersion obtained in Production Example 2 was used instead of the cellulose nanofiber dispersion obtained in Production Example 1.
[0188] <Example 3> A sheet of a crosslinked rubber composition was obtained by carrying out the same treatment as in Example 1, except that the cellulose nanofiber dispersion obtained in Production Example 3 was used instead of the cellulose nanofiber dispersion obtained in Production Example 1.
[0189] <Example 4> In the [mixing step], a styrene-butadiene (SBR)-based latex (Nipol LX407S12, manufactured by Zeon Corporation, solid content concentration 45%) was used instead of natural rubber latex, and the same treatment as in Example 1 was carried out to obtain a water-contact treated cellulose nanofiber / SBR rubber composition. In the [preparation of rubber compound] using the obtained rubber composition, the rubber compound was obtained in the same manner as in Example 1, except that additives were added to 100 parts by mass of the rubber component, namely, 1.5 parts by mass of sulfur (Mucron OT-20, manufactured by Shikoku Kasei Corporation), 2 parts by mass of zinc oxide, 2 parts by mass of antioxidant (ANTAGE RD), 2 parts by mass of stearic acid (50S stearic acid, manufactured by New Japan Chemical Industry Co., Ltd.), and 2 parts by mass of vulcanization accelerator (Noccela MSA-G, manufactured by Ouchi Shinko Chemical Industry Co., Ltd.). In the [crosslinking step], a sheet of the crosslinked rubber composition having a thickness of 2 mm was prepared by pressing and heating at 165°C for 10 minutes.
[0190] <Example 5> A sheet of a crosslinked rubber composition was obtained in the same manner as in Example 1, except that an acrylonitrile-butadiene (NBR)-based latex (Nipol LX513, manufactured by Zeon Corporation, solids concentration 45%) was used instead of natural rubber latex.
[0191] <Example 6> A sheet of a crosslinked rubber composition was obtained in the same manner as in Example 1, except that a carboxy-modified acrylonitrile-butadiene (XNBR)-based latex (Nipol LX551, manufactured by Zeon Corporation, solids concentration 45%) was used instead of the natural rubber latex.
[0192] <Example 7> A rubber compound was obtained in the same manner as in Example 1, except that in [Preparation of compound sheet] of Example 1, 1.5 parts by mass of sulfur, 2 parts by mass of vulcanization accelerator aid, 2 parts by mass of antioxidant (ANTAGE RD), 2 parts by mass of stearic acid, and 2 parts by mass of vulcanization accelerator were added relative to 100 parts by mass of the rubber component. In the [Crosslinking step], a sheet of the crosslinked rubber composition having a thickness of 2 mm was prepared by pressing and heating at 150°C for 10 minutes.
[0193] <Example 8> In the [water contact step], the same treatment as in Example 1 was carried out except that the water temperature was set to 23° C., to obtain a sheet of a crosslinked rubber composition.
[0194] <Example 9> In the [water contact step], the same treatment as in Example 1 was carried out except that the sheet was brought into contact with water by applying running water at a temperature of 60° C. for 5 minutes, to obtain a sheet of the crosslinked rubber composition.
[0195] <Example 10> The same treatment as in Example 1 was carried out except that in the [water contact step], water at a temperature of 60° C. was sprayed at 25 kg / h for 5 minutes to bring the sheet into contact with water, thereby obtaining a sheet of the crosslinked rubber composition.
[0196] <Comparative Example 1> The same treatment as in Example 1 was carried out except for omitting the water contact step, to obtain a sheet of a crosslinked rubber composition.
[0197] <Comparative Example 2> The same treatment as in Example 2 was carried out except for omitting the water contact step, to obtain a sheet of a crosslinked rubber composition.
[0198] <Comparative Example 3> The same treatment as in Example 3 was carried out except for omitting the water contact step, to obtain a sheet of a crosslinked rubber composition.
[0199] <Comparative Example 4> The same treatment as in Example 4 was carried out except for omitting the water contact step, to obtain a sheet of a crosslinked rubber composition.
[0200] <Comparative Example 5> The same treatment as in Example 5 was carried out except for omitting the water contact step, to obtain a sheet of a crosslinked rubber composition.
[0201] <Comparative Example 6> The same treatment as in Example 6 was carried out except for omitting the water contact step, to obtain a sheet of a crosslinked rubber composition.
[0202] <Comparative Example 7> The same treatment as in Example 7 was carried out except for omitting the water contact step, to obtain a sheet of a crosslinked rubber composition.
[0203] <Reference example 1> The natural rubber latex was spread on a tray with a Teflon (registered trademark) surface and dried in an explosion-proof dryer at 40°C for 48 hours to obtain a sheet-shaped natural rubber composition. The same treatment as in Comparative Example 1 was carried out except that this natural rubber composition was used to obtain a sheet of crosslinked rubber composition.
[0204] [Moisture content] The rubber compositions obtained by each step of Examples 1 to 10, Comparative Examples 1 to 7, and Reference Example 1 were placed in a weighing container such as an aluminum cup, the mass was measured, and the composition was placed in a dryer at 105° C. After 3 hours or more had passed, the rubber compositions were recovered and left to stand in a desiccator for 30 seconds, and then the mass was measured. Moisture content (%)=(AB) / A×100 (Here, A is the mass before drying and B is the mass after drying).
[0205] [Water absorption rate] The sheets of the crosslinked rubber compositions obtained in Examples 1 to 10, Comparative Examples 1 to 7, and Reference Example 1 were cut into 1 cm squares, and their masses were measured in an environment of 23° C. and 50% RH, and then immersed in ion-exchanged water at 23° C. for 72 hours. The masses were measured after wiping off the moisture on the surfaces. Water absorption rate (%)=(W-Wo) / Wo×100 (Wo is the mass in a 23°C, 50% RH environment, and W is the mass after immersion in ion-exchanged water for 72 hours).
[0206] [Tensile test] For the sheets of the crosslinked rubber compositions obtained in Examples 1 to 10, Comparative Examples 1 to 7, and Reference Example 1, test pieces were punched into the shape of a dumbbell (dumbbell No. 6) as described in JIS K 6251:2017. A tensile test was performed on the test pieces using a tensile tester Tensilon (manufactured by A&D Corporation) at 23±2°C, a gauge length of 25 mm, and a tensile speed of 500 mm / min in accordance with JIS K 6251:2017 to measure the 50% modulus (σ50 (MPa)), tensile strength (MPa), and elongation at break (%).
[0207] [Table 1-1]
[0208] [Table 1-2]
[0209] According to the method for producing a rubber composition of the present embodiment, a rubber composition was obtained which can give a crosslinked rubber and a crosslinked rubber product having excellent mechanical properties and water resistance. On the other hand, the crosslinked rubbers obtained from the rubber compositions of Comparative Examples 1 to 7, which did not have a water contact step, had high water absorption and poor water resistance. The rubber composition of Reference Example 1, which did not contain fibrous cellulose, had low water absorption but poor mechanical properties. [Industrial Applicability]
[0210] According to the method for producing a rubber composition of the present embodiment, there is provided a rubber composition which gives a crosslinked rubber composition and a crosslinked rubber product which are excellent in mechanical properties and water resistance after crosslinking. [Explanation of symbols]
[0211] 10...double drum dryer, 1...cylinder, 2...feed section, 3...sheet mixture, 4...scraper, 5...composite material
Claims
1. Preparing a solid rubber composition containing a rubber component and fibrous cellulose; a water contacting step of contacting the solid rubber composition with a liquid containing water; and A drying step of drying the solid rubber composition that has been in contact with the water-containing liquid. A method for producing a rubber composition.
2. The method for producing a rubber composition according to claim 1 , wherein in the water contact step, the temperature of the water-containing liquid is 60° C. or higher.
3. The method for producing a rubber composition according to claim 1 , wherein the fibrous cellulose contains fine fibrous cellulose having a fiber width of 1,000 nm or less.
4. The method for producing a rubber composition according to claim 1 , wherein the fibrous cellulose contains coarse cellulose fibers having a fiber width of more than 1 μm.
5. providing a solid rubber composition, A step of mixing a latex containing a rubber component with an aqueous dispersion containing fibrous cellulose to obtain a mixed liquid; and drying the mixture. A method for producing the rubber composition according to claim 1.
6. The step of preparing the solid rubber composition comprises: A step of mixing a latex containing a rubber component with an aqueous dispersion containing fibrous cellulose to obtain a mixed liquid; drying the mixture; and masticating the obtained dried product in this order.
7. The step of preparing the solid rubber composition comprises: A step of mixing a latex containing a rubber component with an aqueous dispersion containing fibrous cellulose to obtain a mixed liquid; drying the mixture; masticating the obtained dried product; and adding a rubber component to the masticated dried product and kneading the rubber component in this order. A method for producing the rubber composition according to claim 1.
8. A step of obtaining a rubber composition by the production method according to any one of claims 1 to 7; and crosslinking and molding the molding rubber composition containing the rubber composition. A method for producing a crosslinked rubber product.
Citation Information
Patent Citations
Composition, and manufacturing method of composition
JP2021123639A
Method for improving nanocellulose dispersion in elastomeric compounds and compositions comprising nanocellulose dispersed in elastomeric compounds
JP2022508946A